Method for manufacturing laminate and printing plate
By combining an ultra-short pulse laser oscillator with a photosensitive resin, a laminate of a support, a photosensitive resin layer and a protective film is formed, which solves the problem that photosensitive resins in the prior art are difficult to form high-precision micro patterns, and improves printing efficiency and quality.
Patent Information
- Application Number
- JP2024077651
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-11
- Filing Date
- 2024-05-13
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2041-03-10
AI Technical Summary
The prior art is difficult to form high-precision micro patterns in the photosensitive resin, and the light absorbing material is difficult to meet good mechanical properties and light transmittance at the same time under near-infrared laser light, resulting in low efficiency in the printing process.
An ultra-short pulse laser oscillator is used to combine with a photosensitive resin to form a laminate including a support, a photosensitive resin layer and a protective film. A micro pattern is formed by ultra-short pulse laser to ensure both light transmittance and mechanical properties.
It realizes efficient formation of micro patterns in photosensitive resin, improves the efficiency and quality of the printing process, and ensures both light transmittance and mechanical properties.
Smart Images

Figure 0007625118000001 
Figure 0007625118000002 
Figure 0007625118000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a laminate and a printing plate. [Background technology]
[0002] Flexographic printing, which is used for printing on various materials such as packaging materials such as cardboard, paper containers, paper bags, and flexible packaging films, building materials such as wallpaper and decorative panels, and labels, has been widely known. In recent years, in the production of printing plates used in flexographic printing, a technology known as flexographic CTP (Computer to Plate) has been developed in which a thin light absorbing layer called a black layer is provided on the surface of a photosensitive resin plate, which is then irradiated with near-infrared laser light to form a mask image directly on the photosensitive resin plate, and light is then irradiated through the mask to cause a crosslinking reaction, after which the non-crosslinked parts of the plate that were not irradiated with light are washed away with a developer. However, although the flexographic CTP narrows down the beam diameter of the near-infrared laser to about 10 μm, the dimension of the pattern that can be formed is limited to 20 μm.
[0003] Another method for producing printing plates has been proposed, which involves irradiating the surface of a resin plate with a laser beam directly to remove the resin in the areas irradiated by the beam, thereby forming a recessed pattern (see, for example, Patent Document 1). Patent Document 1 discloses a laser engraving method in which a photosensitive resin cured product, which has been mixed with carbon black and photocured, is irradiated with the fundamental wave (wavelength: 1.06 μm) of a near-infrared YAG laser to form a pattern, in order to form a more precise pattern. By shortening the oscillation wavelength of the laser used for engraving in this way, it is possible to narrow the laser beam diameter, but in order to make engraving using this near-infrared laser possible, some ingenuity is required, as described below.
[0004] That is, since general organic compounds do not have strong light absorption in the near-infrared wavelength region, it is necessary to mix a dye or pigment having strong light absorption properties in the wavelength region into the photosensitive resin so that the photosensitive resin absorbs the light of the near-infrared laser. The above-mentioned Patent Document 1 also describes mixing a black pigment called carbon black into the photosensitive resin for near-infrared absorption. However, the black pigments and the like have strong light absorption properties even in the ultraviolet region and have low ultraviolet light transmittance, so when a photosensitive resin cured with ultraviolet light is used for laser engraving, the ultraviolet light does not penetrate to the inside of the resin, which is a serious problem in that the photosensitive resin cured product does not have sufficient mechanical properties. Therefore, in a photosensitive resin system to which a near-infrared laser light absorbing material has been added, it is an extremely difficult task to ensure both laser engraving properties and mechanical properties.
[0005] Furthermore, continuous wave near-infrared lasers and pulsed near-infrared lasers with small peak output have traditionally been used to engrave cured photosensitive resins, but there is a problem in that the energy generated by these lasers at their oscillation wavelengths is insufficient to engrave materials with low light absorption characteristics. For example, the pulsed near-infrared YAG laser used in the examples of Patent Document 1 has a relatively large average output, but the pulse width is as wide as about 200 ms, so the peak output is small, and the energy is insufficient to process materials with low light absorption characteristics in which the amount of near-infrared absorbent added is kept low.Furthermore, since the oscillation frequency of the laser is extremely low at 10 Hz, there is also the problem that the processing speed is extremely slow.
[0006] On the other hand, continuous wave near-infrared lasers with a high average output and pulsed near-infrared lasers with an excessively high peak output have high energy, which can cause thermal melting or the like in the material to be engraved, resulting in the formation of recesses with excessive dimensions and drooping of the pattern edges, making it difficult to form fine patterns. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 2846954 Summary of the Invention [Problem to be solved by the invention]
[0008] In view of the above, there is a need for a laminate for producing a printing plate that enables the formation of a fine pattern on a printing original plate using a cured product of a photosensitive resin and that can improve the efficiency of the plate-making process, and a method for producing a printing plate using the same.
[0009] Therefore, the present invention aims to provide a laminate that can be applied to a manufacturing method of a printing plate using a laser engraving method in which a fine concave-convex pattern is formed by irradiating an ultrashort pulsed laser beam, and also to provide a manufacturing method of a printing plate that improves the efficiency of the plate making process. [Means for solving the problem]
[0010] As a result of intensive research into solving the above-mentioned problems, the inventors have found that the above-mentioned problems can be solved by a laminate having a support, a printing original plate, and a protective film, wherein the printing original plate is a printing original plate for forming a concave-convex pattern with ultrashort pulsed laser light and contains a resin cured product obtained by exposing a photosensitive resin to light and curing it over the entire surface, and have thus completed the present invention. That is, the present invention is as follows.
[0011] [1] A laminate comprising a support, a printing plate, and a protective film, the printing plate including a cured resin product formed by exposing a photosensitive resin on the side facing the protective film to light and curing the entire surface of the photosensitive resin. [2] A laminate comprising a support, a printing original plate, and a protective film, the printing original plate being a printing original plate for forming a concave-convex pattern with an ultrashort pulsed laser beam. [3] The printing plate has a storage modulus G' of 5.00×10 at 140° C. 4 Pa or more 1.00×10 6 The laminate according to [1] or [2] above, wherein the elastic modulus is 0.001 Pa or less. [4] The laminate according to any one of [1] to [3] above, wherein the MFR of the printing original plate is 0 or more and 20 (g / 10 min) or less. [5] The laminate according to any one of [1] to [4] above, wherein the printing original plate is a printing original plate for forming a concave-convex pattern with an ultrashort pulsed laser beam. [6] The laminate described in any one of [1] to [5] above, wherein the printing original plate has a light transmittance of 10% or more and 99.9% or less at the wavelength of the ultrashort pulsed laser light for forming the concave-convex pattern. [7] The laminate described in any one of [1] to [6], wherein the printing original plate has a light transmittance of more than 75% and not more than 99.9% at the wavelength of the ultrashort pulsed laser light used to form the concave-convex pattern. [8] The laminate according to any one of [1] to [7] above, wherein the printing original plate contains a photosensitive resin that is photodecomposable, photopolymerizable, or photocrosslinkable when irradiated with actinic radiation. [9] A method for producing a printing plate, comprising a laser engraving step of forming a concave-convex pattern on a surface of the printing plate of the laminate described in any one of [1] to [8] above, using an ultrashort pulsed laser beam.
[10] The printing plate has a storage modulus G' of 5.00×10 at 140° C. 4 Pa or more 1.00×10 6 The method for producing a printing plate according to [9] above,
[11] The method for producing a printing plate according to [9] or
[10] above, wherein an overlap rate between successive pulses of the ultrashort pulsed laser light is 50% or more and 99% or less.
[12] The method for producing a printing plate according to any one of [9] to
[11] above, wherein a lens having a numerical aperture (NA) of 0.010 or more and 0.100 or less is used in the step of forming a concave-convex pattern on the surface of the printing original plate by the ultrashort pulsed laser light.
[13] The method for producing a printing plate according to any one of [9] to
[12] above, wherein the focus depth of the ultrashort pulsed laser beam is 25 μm or more and 700 μm or less from the surface of the printing master plate.
[14] The method for producing a printing plate according to any one of [9] to
[13] above, wherein the printing original plate has a light transmittance of 10% or more and 99.9% or less at the wavelength of the ultrashort pulsed laser light used in the laser engraving process.
[15] The method for producing a printing plate according to any one of [9] to
[14] above, wherein the printing original plate has a light transmittance of more than 75% and not more than 99.9% at the wavelength of the ultrashort pulsed laser light used in the laser engraving step.
[16] The method for producing a printing plate according to any one of [9] to
[15] above, wherein the light source of the ultrashort pulsed laser light used in the laser engraving step has an average output of 0.01 W or more and less than 1000 W.
[17] The method for producing a printing plate according to any one of [9] to
[16] above, wherein the pulse width of the ultrashort pulsed laser beam used in the laser engraving step is 1 femtosecond or more and 200 nanoseconds or less.
[18] The method for producing a printing plate according to any one of [9] to
[17] above, wherein the ultrashort pulsed laser light used in the laser engraving step has an oscillation wavelength of 300 nm or more and 1.5 μm or less.
[19] The method for producing a printing plate according to any one of [9] to
[18] above, wherein the oscillation wavelength of the ultrashort pulsed laser light used in the laser engraving step is 300 nm or more and less than 700 nm.
[20] The method for producing a printing plate according to any one of [9] to
[19] above, wherein the energy per pulse of the ultrashort pulsed laser light used in the laser engraving step is 1 μJ or more and 100 kJ or less. 〔twenty one〕 The method for producing a printing plate according to any one of [9] to
[20] above, wherein the ultrashort pulsed laser light used in the laser engraving step has a repetition frequency of 20 kHz or more and 500 MHz or less. Effect of the Invention
[0012] According to the present invention, it is possible to provide a laminate for producing a printing plate, which is capable of forming a fine pattern on a printing original plate containing a cured product of a photosensitive resin and capable of improving the efficiency of the plate-making process, and a method for producing a printing plate using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention (hereinafter simply referred to as "the present embodiment") will be described in detail. The following embodiments are merely illustrative for explaining the present invention, and are not intended to limit the present invention to the following contents. The present invention can be modified appropriately within the scope of the gist thereof.
[0014] [Laminate] (First laminate) The first laminate of this embodiment has a support, a printing plate, and a protective film, and the printing plate contains a resin composition in which a photosensitive resin on the side facing the protective film is exposed to light and cured over the entire surface. That is, at least the outermost surface of the printing plate facing the protective film is exposed to light and cured over the entire surface. It is preferable that the photosensitive resin of the printing plate is exposed to light and cured over the entire surface in the thickness direction.
[0015] (Second laminate) The second laminate of the present embodiment is a laminate having a support, an original printing plate, and a protective film, and the original printing plate is an original printing plate for forming a concave-convex pattern with ultrashort pulsed laser light. In the laminate of this embodiment, the term "ultrashort pulsed laser light" refers to electromagnetic pulsed laser light on the time order of several hundred picoseconds or less, and includes light on the time order of femtoseconds to attoseconds.
[0016] The first laminate and second laminate (hereinafter sometimes simply referred to as the laminate) of this embodiment make it possible to form fine patterns on a printing original plate and improve the efficiency of printing plate making.
[0017] (Support) The support constituting the laminate of the present embodiment is not particularly limited as long as it can support a printing original plate containing a photosensitive resin or a printing original plate containing a cured product of a photosensitive resin. Examples of materials for the support include, but are not limited to, polyester resin, polyimide resin, polyamide resin, polyamideimide resin, polyetherimide resin, polybismaleimide resin, polysulfone resin, polycarbonate resin, polyphenylene ether resin, polyphenylene thioether resin, polyethersulfone resin, liquid crystal resin made of aromatic polyester resin, aromatic polyamide resin, and epoxy resin. The shape, thickness, and dimensions of the support are not particularly limited, and a shape can be selected according to the application. For example, a sheet shape or a cylindrical shape is given as a suitable shape. The support used when the laminate of this embodiment is formed into a sheet or cylindrical shape will be described in detail below in the section (printing original plate).
[0018] (original printing version) The printing original plate constituting the laminate of this embodiment is preferably a printing original plate for forming a relief pattern with ultrashort pulsed laser light described below, and is preferably a printing original plate in which the photosensitive resin on the side facing the protective film is exposed to light over its entire surface, contains a cured resin product, and is preferably a photosensitive resin that has been exposed to light and cured in the thickness direction as well. The constituent materials of the printing plate may contain, in addition to the photosensitive resin, a photopolymerization initiator described below, a dye as a near-infrared absorbing agent, an inorganic porous material, etc. In other words, the printing plate is preferably a cured product of a photosensitive resin composition containing the above-mentioned components in addition to the photosensitive resin. The resin cured product may be a photosensitive resin cured product having light transmittance in the near-infrared region and ultraviolet region, and examples of the photosensitive resin cured product that can be used include photosensitive resin cured products obtained by photocuring a photosensitive resin such as a photosensitive solid resin or a photosensitive liquid resin whose main component is a thermoplastic resin. The photosensitive resin cured product is preferably a product obtained by molding a liquid photosensitive resin composition at 140° C. and photocuring it, which allows good thickness accuracy and dimensional accuracy to be obtained when the printing original plate is molded into a sheet or cylindrical shape. The photosensitive resin composition preferably has a viscosity at 140° C. of 10 Pa·s or more and 10 kPa·s or less, and more preferably 50 Pa·s or more and 5 kPa·s or less. By having a viscosity of 10 Pa·s or more, the mechanical strength of the produced printing blank will be sufficient, and the printing blank will be easily able to retain its shape and be easily processed even when molded into a cylindrical printing blank.
[0019] It is preferable that the viscosity of the photosensitive resin composition at 140°C is 10 kPa s or less, from the viewpoints that the composition is easily deformed and processed when a laminate is produced at 140°C or higher, is easily molded into a sheet-shaped or cylindrical printing blank, and the molding process is simple. In particular, in order to obtain a cylindrical printing original plate with high plate thickness accuracy, in order to prevent dripping and the like when forming a liquid photosensitive resin composition layer on a cylindrical support, the viscosity at 140°C is preferably 10 Pa·s or more, more preferably 100 Pa·s or more, even more preferably 200 Pa·s or more, and even more preferably 300 Pa·s or more. Furthermore, when the photosensitive resin composition used in the printing original plate of this embodiment is liquid, particularly at 140°C, it is preferable that the photosensitive resin composition has thixotropy, from the viewpoint of being able to maintain a predetermined thickness without causing liquid dripping due to gravity when forming a photosensitive resin composition layer on a cylindrical support.
[0020] The printing original plate constituting the laminate of this embodiment preferably contains a photosensitive resin that is photodecomposable, photopolymerizable, or photocrosslinkable when irradiated with actinic radiation. Actinic radiation refers to electromagnetic radiation such as gamma radiation, x-rays, ultraviolet radiation, near ultraviolet radiation, visible light, and near infrared radiation. When the photosensitive resin is photodecomposable upon exposure to actinic radiation, the solubility of the photosensitive resin in a solvent can be increased, and the volatility of the photosensitive resin can be increased, which makes it easier to form a relief pattern on the surface of the original printing plate. Examples of such photosensitive resins include photoresists and photosensitive polyimides. The photosensitive resin has photopolymerizability or photocrosslinkability upon exposure to actinic radiation, which improves the swelling resistance of the photosensitive resin when immersed in a solvent and improves the heat resistance when stored in a high-temperature environment. Examples of such photosensitive resins include photosensitive resins used in existing master plates for flexographic printing plates.
[0021] The printing original plate constituting the laminate of this embodiment preferably contains a thermoplastic elastomer (a), which is a polymer that becomes plasticized and moldable at high temperatures and exhibits the properties of a rubber elastic body at room temperature, from the viewpoint of achieving good engraving properties with an ultrashort pulsed laser beam, mechanical properties, and solvent resistance. From the viewpoints of moldability, shortening the plate-making time, and image reproducibility of the printing plate, it is preferable that the thermoplastic elastomer (a) is composed of a polymer block mainly composed of at least one vinyl aromatic hydrocarbon unit (hereinafter simply referred to as vinyl aromatic hydrocarbon) and a polymer block mainly composed of at least one conjugated diene unit (hereinafter simply referred to as conjugated diene). In this specification, the term "mainly composed of" refers to being contained in the polymer block at 50% by mass or more. Examples of vinyl aromatic hydrocarbons include, but are not limited to, monomers such as styrene, p-methylstyrene, tertiary butylstyrene, α-methylstyrene, 1,1-diphenylethylene, vinyltoluene, etc., with styrene being particularly preferred. These monomers may be used alone or in combination of two or more. Conjugated dienes include, but are not limited to, butadiene and isoprene, and butadiene is particularly preferred from the viewpoint of wear resistance. These monomers may be used alone or in combination of two or more. In order to further improve solvent resistance, hydrogen may be added to the double bond in the conjugated diene as necessary. The photosensitive resin composition used in the original printing plate preferably contains the thermoplastic elastomer (a) which is the polymer compound, an organic compound (b) having a polymerizable unsaturated group in the molecule, and a photopolymerization initiator (c). The thermoplastic elastomer (a) is preferably a compound having a number average molecular weight of 1000 or more and 300,000 or less. The number average molecular weight of the thermoplastic elastomer (a) is more preferably 2000 or more and 200,000 or less, and further preferably 50,000 or more and 150,000 or less. It is preferable that the number average molecular weight of the thermoplastic elastomer (a) is 1,000 or more, from the viewpoints that the printing original plate prepared by crosslinking in a later step will have sufficient strength, and that a printing plate having a relief image prepared from the printing original plate will be able to withstand repeated use. In addition, it is preferable that the number average molecular weight of the thermoplastic elastomer (a) is 300,000 or less, from the viewpoint that the viscosity of the photosensitive resin composition does not increase excessively during molding processing, and a sheet-shaped or cylindrical printing original plate can be easily produced. In this specification, the number average molecular weight is a value measured by gel permeation chromatography and calibrated with polystyrene of known molecular weight.
[0022] The thermoplastic elastomer (a) may be a compound having a polymerizable unsaturated group in the molecule. The number average molecular weight of the thermoplastic elastomer (a) is larger than that of the "organic compound (b) having a polymerizable unsaturated group in the molecule," and in this respect, the thermoplastic elastomer is distinguished from the organic compound (b). The "polymerizable unsaturated group" refers to a polymerizable unsaturated group that is involved in a radical polymerization reaction or an addition polymerization reaction. Examples of the polymerizable unsaturated group involved in the radical polymerization reaction include, but are not limited to, a vinyl group, an acetylene group, an acrylic group, and a methacrylic group. Examples of polymerizable unsaturated groups participating in an addition polymerization reaction include, but are not limited to, a cinnamoyl group, a thiol group, an azide group, an epoxy group that undergoes a ring-opening addition reaction, an oxetane group, a cyclic ester group, a dioxirane group, a spiro orthocarbonate group, a spiro orthoester group, a bicyclo orthoester group, and a cyclic imino ether group. Particularly preferred thermoplastic elastomers (a) include polymers having an average of 0.7 or more polymerizable unsaturated groups per molecule, and more preferably an amount of more than 1 polymerizable unsaturated group per molecule. The average number of polymerizable unsaturated groups per molecule is preferably 0.7 or more, since the printing plate obtained from the photosensitive resin composition has excellent mechanical strength and the relief shape is less likely to be distorted when engraved with an ultrashort pulsed laser beam, and further, the durability is good and the printing plate can withstand repeated use. The position of the polymerizable unsaturated group in the thermoplastic elastomer (a) is preferably directly bonded to the end of the polymer main chain, the end of the polymer side chain, or in the polymer main chain or side chain. The average number of polymerizable unsaturated groups contained in one molecule of the thermoplastic elastomer (a) can be determined by molecular structure analysis using nuclear magnetic resonance spectroscopy (NMR method).
[0023] In particular, the following method is suitable for introducing a polymerizable unsaturated group into the molecular terminal of the thermoplastic elastomer (a). That is, first, a binder having a molecular weight of several thousand and a plurality of groups capable of bonding with the reactive groups of the thermoplastic elastomer (a) component (e.g., polyisocyanate in the case of hydroxyl or amino groups) having a plurality of reactive groups such as hydroxyl, amino, epoxy, carboxyl, acid anhydride, ketone, hydrazine, isocyanate, isothiocyanate, cyclic carbonate, alkoxycarbonyl, etc. is reacted with the reactive groups of the thermoplastic elastomer (a) to adjust the molecular weight of the thermoplastic elastomer (a). Next, the terminals of the thermoplastic elastomer (a) are converted to binding groups. Then, an organic compound having a group that reacts with the bonding group at the end of the thermoplastic elastomer (a) and a predetermined polymerizable unsaturated group is reacted with the thermoplastic elastomer (a) to introduce the polymerizable unsaturated group at the end of the thermoplastic elastomer (a).
[0024] As the "thermoplastic elastomer (a)", a compound having a carbonate group, a carbamate group, or a methacryl group in the polymer main chain is preferred because of its high resistance to thermal decomposition. For example, examples of polymers having good thermal decomposition resistance include polyesters and polyurethanes synthesized using (poly)carbonate diols or (poly)carbonate dicarboxylic acids as raw materials, and polyamides synthesized using (poly)carbonate diamines as raw materials. These polymers may contain polymerizable unsaturated groups in the main chain and / or side chain. When the thermoplastic elastomer (a) has a reactive functional group such as a hydroxyl group, an amino group, or a carboxyl group at its terminal, it is also easy to introduce a polymerizable unsaturated group into the main chain terminal of the thermoplastic elastomer (a). As the "thermoplastic elastomer (a)", a compound having at least one bond selected from a carbonate bond and an ester bond in the molecule, and at least one bond selected from a urethane bond, a urea bond, and an amide bond is particularly preferred. By using such a compound, a printing plate blank having better laser engraving properties, mechanical properties, and solvent resistance can be obtained.
[0025] Other examples of the thermoplastic elastomer (a) include polymer compounds in which a polymerizable unsaturated group is introduced into the molecule of a polymer compound having no polymerizable unsaturated group as a starting material by a chemical reaction such as a substitution reaction, elimination reaction, condensation reaction, or addition reaction. Examples of the polymeric compound having no polymerizable unsaturated group as the starting material include polyolefins such as polyethylene and polypropylene; polyhaloolefins such as polyvinyl chloride and polyvinylidene chloride; CC chain polymers such as polystyrene, polyacrylonitrile, polyvinyl alcohol, polyvinyl acetate, polyvinyl acetal, polyacrylic acid, poly(meth)acrylic acid esters, poly(meth)acrylamide and polyvinyl ether; polyethers such as polyphenylene ether; polythioethers such as polyphenylene thioether; polyesters such as polyethylene terephthalate; polymer compounds such as polycarbonate, polyacetal, polyurethane, polyamide, polyurea, polyimide and polydialkylsiloxane, or polymer compounds having a heteroatom in the main chain of these polymer compounds; and random copolymers and block copolymers synthesized from a plurality of types of monomer components. Furthermore, as the thermoplastic elastomer (a), a mixture of multiple polymeric compounds having polymerizable unsaturated groups introduced into the molecule can also be used.
[0026] In particular, when the laminate of the present embodiment is used for a flexographic printing plate, a flexible relief image is required, and therefore the thermoplastic elastomer (a) preferably contains a liquid resin having a glass transition temperature of 20° C. or lower, and more preferably contains a liquid resin having a glass transition temperature of 0° C. or lower. The content of the liquid resin is preferably 5% by mass or more based on the total amount of the thermoplastic elastomer (a). Examples of such liquid resins include, but are not limited to, hydrocarbons such as polyethylene, polybutadiene, hydrogenated polybutadiene, polyisoprene, hydrogenated polyisoprene, and liquid paraffin; polyesters such as adipate and polycaprolactone; polyethers such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; silicones such as aliphatic polycarbonate and polydimethylsiloxane; polymers of (meth)acrylic acid and / or derivatives thereof, and mixtures or copolymers thereof, and compounds having a polymerizable unsaturated group in the molecule that are synthesized using these polymers. As the liquid resin, polyethylene, polybutadiene, and hydrogenated polybutadienes are particularly preferred from the viewpoint of weather resistance. In this specification, the term "liquid resin" refers to a polymeric substance that has the property of being easily fluid and deformed and being able to solidify in the deformed shape by cooling, and corresponds to an elastomer that has the property of being instantly deformed in response to the application of an external force and recovering to its original shape in a short time when the external force is removed. Since the thermoplastic elastomer (a) contains a liquid resin having a glass transition temperature of 20°C or lower, the photosensitive resin composition can be easily adjusted to a liquid state at 140°C. As a result, when the printing plate, which is a cured product of the photosensitive resin composition, is molded into a sheet or cylinder, good thickness accuracy and dimensional accuracy can be obtained.
[0027] The organic compound (b) contained in the photosensitive resin composition is a compound having a polymerizable unsaturated group in the molecule. From the viewpoint of ease of mixing with the above-mentioned thermoplastic elastomer (a), the number average molecular weight of the organic compound (b) is preferably less than 1,000. The polymerizable unsaturated group is defined as a polymerizable unsaturated group which is involved in a radical polymerization reaction or an addition polymerization reaction, as described in the section on the thermoplastic elastomer (a). Examples of the polymerizable unsaturated group involved in the radical polymerization reaction include, but are not limited to, a vinyl group, an acetylene group, an acrylic group, and a methacrylic group. Examples of polymerizable unsaturated groups involved in an addition polymerization reaction include, but are not limited to, a cinnamoyl group, a thiol group, an azide group, an epoxy group that undergoes a ring-opening addition reaction, an oxetane group, a cyclic ester group, a dioxirane group, a spiro orthocarbonate group, a spiro orthoester group, a bicyclo orthoester group, and a cyclic imino ether group.
[0028] Examples of the organic compound (b) include, but are not limited to, olefins such as ethylene, propylene, styrene, and divinylbenzene; acetylenes, (meth)acrylic acid and derivatives thereof; unsaturated nitriles such as haloolefins and acrylonitrile; (meth)acrylamide and derivatives thereof; aryl compounds such as aryl alcohols and aryl isocyanates; unsaturated dicarboxylic acids and derivatives thereof such as maleic anhydride, maleic acid, and fumaric acid; vinyl acetates, N-vinylpyrrolidone, and N-vinylcarbazole. From the viewpoints of variety, price, and polymerization reactivity, (meth)acrylic acid and derivatives thereof are preferred. Examples of derivatives of the various compounds include compounds having an alicyclic skeleton such as a cycloalkyl, bicycloalkyl, cycloalkene, or bicycloalkene; compounds having an aromatic skeleton such as a benzyl, phenyl, phenoxy, or fluorene; compounds having an alkyl group, a halogenated alkyl group, an alkoxyalkyl group, a hydroxyalkyl group, an aminoalkyl group, or a glycidyl group; ester compounds with polyhydric alcohols such as alkylene glycol, polyoxyalkylene glycol, polyalkylene glycol, or trimethylolpropane; and compounds having a polysiloxane structure such as polydimethylsiloxane or polydiethylsiloxane. The organic compound (b) may be a heteroaromatic compound containing elements such as nitrogen and sulfur.
[0029] In addition, examples of the compound having an epoxy group that undergoes an addition polymerization reaction as the organic compound (b) include, but are not limited to, compounds obtained by reacting epichlorohydrin with polyols such as various diols and triols; epoxy compounds obtained by reacting a peracid with an ethylene bond in the molecule; and the like. Specific examples of such organic compounds (b) include ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, triethylene glycol diglycidyl ether, tetraethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, trimethylol ... Examples of epoxy compounds include dipropane triglycidyl ether, bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, diglycidyl ether of a compound in which ethylene oxide or propylene oxide is added to bisphenol A, polytetramethylene glycol diglycidyl ether, poly(propylene glycol adipate)diol diglycidyl ether, poly(ethylene glycol adipate)diol diglycidyl ether, poly(caprolactone)diol diglycidyl ether, and epoxy-modified silicone oils (for example, trade name "HF-105" manufactured by Shin-Etsu Chemical Co., Ltd.).
[0030] The organic compound (b) having a polymerizable unsaturated group contained in the photosensitive resin composition may be selected from one or more types depending on the purpose. In order to suppress swelling of a printing plate produced using the laminate of this embodiment in organic solvents such as alcohols and esters, which are used as the solvent for printing inks, it is preferable to use at least one type of derivative of a long-chain aliphatic, alicyclic, or aromatic compound as the organic compound (b). In order to increase the mechanical strength of a printing original plate produced using the laminate of this embodiment, it is preferable to use at least one derivative of an alicyclic or aromatic compound as the organic compound (b). In these cases, the content of the derivative of the long-chain aliphatic, alicyclic or aromatic compound is preferably 2 mass % or more, more preferably 5 mass % or more, of the total amount of the organic compound (b). The derivative of the aromatic compound may be an aromatic compound containing an element such as nitrogen or sulfur.
[0031] The printing original plate constituting the laminate of this embodiment is, as described above, a resin cured product obtained by exposing the photosensitive resin on the side facing the protective film to light and curing the entire surface of the resin, and is particularly preferably a resin cured product that is exposed to light and cured in the thickness direction as well. From this viewpoint, it is preferable to add a photopolymerization initiator (c) to the photosensitive resin composition. As the photopolymerization initiator (c), a commonly used one can be selected, and although not limited thereto, for example, initiators for radical polymerization, cationic polymerization, and anionic polymerization exemplified in "Polymer Data Handbook - Basics" edited by the Society of Polymer Science, published by Baifukan in 1986, can be used. Furthermore, crosslinking by photopolymerization using a photopolymerization initiator is useful from the viewpoint of enabling production of a printing original plate with high productivity while maintaining the storage stability of the photosensitive resin composition. As photopolymerization initiators that induce radical polymerization reactions, hydrogen abstraction type photopolymerization initiators (d) and decomposition type photopolymerization initiators (e) are used as particularly effective photopolymerization initiators.
[0032] The hydrogen abstraction type photopolymerization initiator (d) is not particularly limited, but it is preferable to use an aromatic ketone. Aromatic ketones can efficiently enter an excited triplet state upon photoexcitation, and this excited triplet state can abstract hydrogen from the surrounding medium to generate radicals, which are believed to be involved in the photocrosslinking reaction. Examples of aromatic ketones include, but are not limited to, benzophenones, Michler's ketones, xanthenes, thioxanthones, and anthraquinones. It is preferable to use at least one compound selected from these groups. Benzophenones refer to benzophenone and its derivatives, and specific examples thereof include 3,3',4,4'-benzophenonetetracarboxylic acid anhydride, 3,3',4,4'-tetramethoxybenzophenone, and the like. Michler's ketones refer to Michler's ketone and its derivatives. Xanthenes refer to xanthene and derivatives in which hydrogen is replaced by an alkyl group, a phenyl group, or a halogen group. Thioxanthones refer to thioxanthone and derivatives in which hydrogen is substituted with an alkyl group, a phenyl group, or a halogen group, and specific examples include ethylthioxanthone, methylthioxanthone, and chlorothioxanthone. The anthraquinones refer to anthraquinone and derivatives in which hydrogen is substituted with an alkyl group, a phenyl group, a halogen group, or the like. The amount of the hydrogen abstraction type photopolymerization initiator (d) added is preferably 0.1% by mass to 10% by mass, more preferably 0.5% by mass to 5% by mass, of the total amount of the photosensitive resin composition. By adding an amount within this range, when the photosensitive resin composition is photocured in the atmosphere, sufficient curability of the cured surface can be ensured, and low degradation can be ensured.
[0033] The decomposition type photopolymerization initiator (e) refers to a compound that undergoes a cleavage reaction within the molecule after absorbing light to generate an active radical. This decomposition type photopolymerization initiator (e) is not limited to the following, but examples thereof include benzoin alkyl ethers, 2,2-dialkoxy-2-phenylacetophenones, acetophenones, acyloxime esters, azo compounds, organic sulfur compounds, diketones, and the like, and it is preferable to use at least one compound selected from these groups. Examples of benzoin alkyl ethers include benzoin isopropyl ether, benzoin isobutyl ether, and the compounds described in "Photosensitive Polymers" (Kodansha, 1977, p. 228). Examples of 2,2-dialkoxy-2-phenylacetophenones include 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, and the like. Examples of acetophenones include acetophenone, trichloroacetophenone, 1-hydroxycyclohexylphenylacetophenone, and 2,2-diethoxyacetophenone. An example of the acyloxime esters is 1-phenyl-1,2-propanedione-2-(o-benzoyl)oxime. Examples of the azo compound include azobisisobutyronitrile, a diazonium compound, and a tetrazene compound. Examples of organic sulfur compounds include aromatic thiols, mono- and disulfides, thiuram sulfides, dithiocarbamates, S-acyldithiocarbamates, thiosulfonates, sulfoxides, sulfenates, dithiocarbonates, and the like. Examples of the diketones include benzyl and methyl benzoyl formate. The amount of the decomposition type photopolymerization initiator (e) added is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.3% by mass or more and 3% by mass or less, based on the total amount of the photosensitive resin composition. By adding an amount within this range, when the photosensitive resin composition is photocured in the atmosphere, the curability of the inside of the cured product can be sufficiently ensured.
[0034] Instead of the hydrogen abstraction type photopolymerization initiator (d) and the degradable type photopolymerization initiator (e), a compound having a site functioning as a hydrogen abstraction type photopolymerization initiator and a site functioning as a degradable type photopolymerization initiator in the same molecule can also be used as the photopolymerization initiator (c). Examples of such photopolymerization initiators include α-aminoacetophenones, specifically 2-methyl-1-(4-methylthiophenyl)-2-morpholino-propan-1-one and compounds represented by the following general formula (1).
[0035] [ka]
[0036] (In formula (1), each R2 independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. Furthermore, X represents an alkylene group having 1 to 10 carbon atoms.)
[0037] The amount of the compound having a moiety that functions as a hydrogen abstraction type photopolymerization initiator and a moiety that functions as a decomposition type photopolymerization initiator in the same molecule is preferably 0.1 mass % or more and 10 mass % or less, and more preferably 0.3 mass % or more and 3 mass % or less, of the total amount of the photosensitive resin composition. The amount added within the above range is preferable from the viewpoint of ensuring sufficient mechanical properties of the cured resin even when the photosensitive resin composition is photocured in the atmosphere. As the photopolymerization initiator, a photopolymerization initiator that absorbs light to generate an acid and induces an addition polymerization reaction can also be used. Such photopolymerization initiators include, but are not limited to, photocationic polymerization initiators such as aromatic diazonium salts, aromatic iodonium salts, and aromatic sulfonium salts, or polymerization initiators that absorb light to generate a base. The amount of these photopolymerization initiators added is preferably 0.1% by mass or more and 10% by mass or less of the total amount of the photosensitive resin composition.
[0038] The photosensitive resin composition used in the original printing plate constituting the laminate of this embodiment may contain a near-infrared absorbing agent within a range that does not impair the object of the present invention. From the viewpoint of ensuring the mechanical properties of the printing original plate, the content of the near infrared absorbing agent in the photosensitive resin composition is preferably 20,000 ppm or less, more preferably 10,000 ppm or less, and further preferably 50 ppm or less. Examples of near-infrared absorbing agents include, but are not limited to, cyanine dyes such as phthalocyanine dyes and heptamethine cyanine dyes, oxonol dyes such as pentamethine oxonol dyes, indolium dyes, benzindolium dyes, benzothiazolium dyes, quinolinium dyes, and phthalide compounds reacted with color developers. Not all cyanine dyes have the above-mentioned light absorption characteristics. The light absorption characteristics change significantly depending on the type and position of the substituent in the molecule, the number of conjugated bonds, the type of counter ion, the surrounding environment in which the dye molecule exists, and the like. In addition, commercially available laser dyes, saturable absorption dyes, and near infrared absorbing dyes can also be used.
[0039] As the laser dye, the near infrared absorbing dye, and the phthalide compound reacted with the color developer, conventionally known dye compounds, and commercially available dye compounds can be appropriately used.
[0040] In addition, when a dye that reacts with a photosensitive resin composition to change the light absorption wavelength is used as a near infrared absorbing agent, it can be used in a state of being contained in microcapsules. As the near infrared absorbing agent, it is also possible to use ion exchanger fine particles having metal ions such as copper, tin, indium, yttrium, rare earth elements, etc. The ion exchanger fine particles may be organic resin fine particles or inorganic fine particles.
[0041] An inorganic porous material (f) may be added to the photosensitive resin composition used in the printing original plate of the laminate of this embodiment. The inorganic porous material (f) is an inorganic particle having minute pores or minute gaps in the particle. The inorganic porous material (f) preferably has a number average particle size of 0.1 to 100 μm, more preferably 0.5 to 20 μm, and further preferably 3 to 10 μm. The average particle size of the inorganic porous material (f) can be measured using a laser scattering type particle size distribution measuring device.
[0042] The inorganic porous body (f) has a specific surface area of 10 m 2 / g or more 1500m 2 / g or less. More preferably, it is 100m 2 / g or more 800m 2 / g or less. The specific surface area of the inorganic porous material (f) can be determined from the nitrogen adsorption isotherm at -196°C based on the BET equation.
[0043] The inorganic porous material (f) has an average pore diameter of preferably 1 nm or more and 1000 nm or less, more preferably 2 nm or more and 200 nm or less, and further preferably 2 nm or more and 50 nm or less. The average pore diameter can be measured using a nitrogen adsorption method. The pore size distribution of the inorganic porous material (f) can be determined from the nitrogen adsorption isotherm at -196°C.
[0044] The inorganic porous material (f) has a pore volume of preferably 0.1 mL / g to 10 mL / g, more preferably 0.2 mL / g to 5 mL / g. The pore volume can be measured by a nitrogen adsorption method and is determined from the nitrogen adsorption isotherm at -196°C. The oil absorption of the inorganic porous material (f) is preferably in the range of 10 mL / 100 g to 2000 mL / 100 g, more preferably in the range of 50 mL / 100 g to 1000 mL / 100 g. The oil absorption can be measured in accordance with JIS-K5101.
[0045] When an inorganic porous material (f) is contained in the photosensitive resin composition used in the printing original plate constituting the laminate of this embodiment, the particle shape of the inorganic porous material (f) is not particularly limited, and examples thereof include spherical, flat, acicular, amorphous, or particles with protrusions on the surface. Examples of the inorganic porous material (f) include, but are not limited to, porous silica, mesoporous silica, silica-zirconia porous gel, porous alumina, and porous glass. The inorganic porous material (f) may be used alone or in combination of two or more kinds.
[0046] In the photosensitive resin composition, the amount of the thermoplastic elastomer (a) and the organic compound (b) is usually preferably 5 to 200 parts by mass, more preferably 20 to 100 parts by mass, of the organic compound (b) per 100 parts by mass of the thermoplastic elastomer (a). When the proportion of organic compound (b) is 5 parts by mass or more, the balance between the hardness and tensile strength / elongation of the resulting printing plate, etc. is good. When the proportion is 200 parts by mass or less, shrinkage during crosslinking hardening can be reduced and thickness precision can be good.
[0047] Various additives such as polymerization inhibitors, ultraviolet absorbers, dyes, pigments, lubricants, surfactants, plasticizers, and fragrances can be blended into the photosensitive resin composition depending on the application and purpose, as long as the object of the present invention is not impaired. The printing original plate constituting the laminate of this embodiment is obtained by photocuring a photosensitive resin composition. At this time, the photocuring may be carried out after forming the photosensitive resin composition into a sheet or a cylinder. As a method for forming the photosensitive resin composition into a sheet or cylinder, an existing resin molding method can be used. For example, a casting method, a method in which a resin is extruded from a nozzle or a die using a machine such as a pump or an extruder, and the thickness is adjusted with a blade, or a method in which the thickness is adjusted by calendaring with a roll, etc. can be mentioned. In this case, the molding can be performed while heating within a range that does not deteriorate the performance of the photosensitive resin composition. In addition, rolling treatment, grinding treatment, etc. may be performed as necessary. Usually, a photosensitive resin composition layer is often molded directly on a sheet-like support made of a material such as PET or nickel, with or without an adhesive layer, but the photosensitive resin composition layer may be molded directly on the cylinder of a printing machine. In addition, a cylindrical support made of fiber reinforced plastic (FRP), plastic, or metal can also be used. As the cylindrical support, a hollow one with a certain thickness may be used to reduce weight. The role of the sheet-like support or cylindrical support is to ensure the dimensional stability of the printing original plate. Therefore, it is preferable to select one with high dimensional stability.
[0048] When the cylindrical support and the sheet-like support are evaluated using the linear thermal expansion coefficient, the linear thermal expansion coefficient is preferably 100 ppm / ° C. or less, and more preferably 70 ppm / ° C. or less, thereby obtaining a printing original plate having high dimensional stability. Materials for the cylindrical support and the sheet-like support include, but are not limited to, polyester resin, polyimide resin, polyamide resin, polyamideimide resin, polyetherimide resin, polybismaleimide resin, polysulfone resin, polycarbonate resin, polyphenylene ether resin, polyphenylene thioether resin, polyethersulfone resin, liquid crystal resin made of wholly aromatic polyester resin, wholly aromatic polyamide resin, epoxy resin, and the like.
[0049] The support may also be formed by laminating the above-mentioned resins. For example, a sheet in which a polyethylene terephthalate layer having a thickness of 50 μm is laminated may be used. In addition, a porous sheet, for example, a cloth formed by weaving fibers, a nonwoven fabric, a film with pores formed therein, etc. can be used as the sheet-like support or the cylindrical support. When a porous sheet or a porous cylinder is used as the sheet-like support or the cylindrical support, the photosensitive resin composition is impregnated into the pores and then photocured, so that the photosensitive resin cured product layer and the sheet-like support or the cylindrical support are integrated to obtain high adhesion. Examples of fibers that form cloth or nonwoven fabric include, but are not limited to, inorganic fibers such as glass fiber, alumina fiber, carbon fiber, alumina-silica fiber, boron fiber, high silicon fiber, potassium titanate fiber, sapphire fiber, etc., natural fibers such as cotton and hemp, semi-synthetic fibers such as rayon and acetate, and synthetic fibers such as nylon, polyester, acrylic, vinylon, polyvinyl chloride, polyolefin, polyurethane, polyimide, aramid, etc. Cellulose produced by bacteria is a highly crystalline nanofiber, and is a material that can be used to fabricate thin nonwoven fabrics with high dimensional stability.
[0050] In addition, examples of methods for reducing the linear thermal expansion coefficient of a sheet-like support or a cylindrical support to 100 ppm / °C or less include a method of adding a filler to the material of these supports, and a method of impregnating or coating a mesh cloth such as a wholly aromatic polyamide or a glass cloth with a resin. Examples of the filler include commonly used organic fine particles, inorganic fine particles such as metal oxides or metals, and organic-inorganic composite fine particles. In addition, porous fine particles, fine particles having internal cavities, microcapsule particles, and layered compound particles in which low molecular weight compounds are intercalated can also be used. In particular, metal oxide fine particles such as alumina, silica, titanium oxide, and zeolite, latex fine particles made of polystyrene-polybutadiene copolymer, and natural organic fine particles such as highly crystalline cellulose are preferred.
[0051] When the laminate of this embodiment is in the form of a sheet or cylinder, the sheet-like support or cylindrical support used can be subjected to a physical or chemical treatment on the surface to improve adhesion to the photosensitive resin composition layer or adhesive layer. Examples of physical treatment methods include, but are not limited to, sandblasting, wet blasting in which a liquid containing fine particles is sprayed, corona discharge treatment, plasma treatment, and ultraviolet or vacuum ultraviolet irradiation. Examples of the chemical treatment method include, but are not limited to, a strong acid / strong alkali treatment method, an oxidizing agent treatment method, a coupling agent treatment method, and the like. The printing original plate constituting the laminate of this embodiment may be one which is obtained by exposing a photosensitive resin composition layer formed on a support to light and crosslinking it, or one which is crosslinked by light irradiation while being formed on a support. Examples of light sources used for exposure curing include UV-LEDs, high pressure mercury lamps, ultra-high pressure mercury lamps, ultraviolet fluorescent lamps, germicidal lamps, carbon arc lamps, xenon lamps, and metal halide lamps. The light irradiated to the photosensitive resin composition layer is preferably light having a wavelength of 200 nm to 400 nm. In particular, since many hydrogen abstraction type photopolymerization initiators (d) have strong light absorption in this wavelength region, when the light irradiated to the photosensitive resin composition layer is light having a wavelength of 200 nm to 300 nm, the curability of the surface of the photosensitive resin cured product layer can be sufficiently ensured. The light source used for curing may be one type, or two or more types of light sources with different wavelengths may be used for curing, which tends to improve the curability of the resin.
[0052] When the printing plate constituting the laminate of this embodiment is used as a printing plate for forming a concave-convex pattern with an ultrashort pulsed laser beam, the thickness of this printing plate can be set arbitrarily depending on the purpose of use, but when a printing plate is finally produced, the thickness is generally in the range of 0.1 to 7 mm. In some cases, a plurality of materials having different compositions may be laminated to adjust the thickness of the printing plate.
[0053] In the laminate of this embodiment, a cushion layer made of an elastomer may be formed below the printing original plate to be laser engraved. The cushion layer is preferably an elastomer layer having a Shore A hardness of 20 degrees to 70 degrees. When the Shore A hardness is 20 degrees or more, the cushion layer deforms appropriately, which is preferable since it is possible to ensure printing quality. Also, when the Shore A hardness is 70 degrees or less, it is preferable since it is possible to function as a cushion layer. A more preferable Shore A hardness range is 30 degrees to 60 degrees.
[0054] The material constituting the cushion layer is not limited to the following, but is preferably, for example, a material having rubber elasticity such as a thermoplastic elastomer, a photocurable elastomer, or a thermosetting elastomer, and may be a layer made of a porous elastomer having fine pores at the nanometer level. In particular, from the viewpoint of processability into a sheet-like or cylindrical printing plate, it is preferable to use an elastomer of a photosensitive resin composition that is liquid at 140° C. and hardens when exposed to light, as this is convenient. Thermoplastic elastomers used in the cushion layer include, but are not limited to, styrene-based thermoplastic elastomers such as SBS (polystyrene-polybutadiene-polystyrene), SIS (polystyrene-polyisoprene-polystyrene), and SEBS (polystyrene-polyethylene / polybutylene-polystyrene), olefin-based thermoplastic elastomers, urethane-based thermoplastic elastomers, ester-based thermoplastic elastomers, amide-based thermoplastic elastomers, silicone-based thermoplastic elastomers, and fluorine-based thermoplastic elastomers.
[0055] Examples of the photocurable elastomer used in the cushion layer include a mixture of the thermoplastic elastomer with a photopolymerizable monomer, a plasticizer, a photopolymerization initiator, etc., and a liquid composition in which a plastomer resin is mixed with a photopolymerizable monomer, a photopolymerization initiator, etc. Unlike the design concept of photosensitive resin compositions, for which the ability to form fine patterns is an important element, the cushion layer does not require the formation of fine patterns using light, and it is sufficient to ensure a certain level of mechanical strength by curing through overall exposure, allowing for extremely high freedom in the selection of materials. In addition, sulfur crosslinking rubber, organic peroxides, phenol resin initial condensates, quinone dioximes, metal oxides, thioureas, and other non-sulfur crosslinking rubbers can also be used. Furthermore, a telechelic liquid rubber that has been three-dimensionally crosslinked with a specific curing agent to form an elastomer can also be used.
[0056] Furthermore, in the laminate of this embodiment, by forming a specified modified layer on the surface of a printing original plate for laser engraving, it is possible to achieve the final targeted reduction in tack on the printing plate surface and improvement in ink wettability. Examples of the modified layer include a coating treated with a compound that reacts with surface hydroxyl groups, such as a silane coupling agent or a titanium coupling agent, and a polymer film containing porous inorganic particles. A widely used silane coupling agent can be a compound having a functional group in the molecule that is highly reactive with the hydroxyl group on the surface of the printing plate. Examples of the functional group that is highly reactive with the hydroxyl group include a trimethoxysilyl group, a triethoxysilyl group, a trichlorosilyl group, a diethoxysilyl group, a dimethoxysilyl group, a dimonochlorosilyl group, a monoethoxysilyl group, a monomethoxysilyl group, and a monochlorosilyl group. At least one of these functional groups is present in the molecule of the compound, and is fixed to the surface of the printing plate by reacting with the hydroxyl group on the surface of the printing plate. Furthermore, as a compound constituting a silane coupling agent, a compound having at least one functional group selected from an acryloyl group, a methacryloyl group, an active hydrogen-containing amino group, an epoxy group, a vinyl group, a perfluoroalkyl group, and a mercapto group as a reactive functional group in the molecule, or a compound having a long-chain alkyl group can be used.
[0057] Examples of the titanium coupling agent include, but are not limited to, isopropyl triisostearoyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, tetraoctyl bis(di-tridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl) bis(di-tridecyl) phosphite titanate, bis(octyl pyrophosphate) oxy Examples of the titanium dioxide include acetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl isostearoyl diacryl titanate, isopropyl tri(dioctyl sulfate) titanate, isopropyl tricumyl phenyl titanate, and tetraisopropyl bis(dioctyl phosphite) titanate.
[0058] In the laminate of this embodiment, when the compound constituting the coupling agent used to form the modified layer on the surface of the printing original plate has a polymerizable reactive group in particular, after fixing these compounds to the surface of the printing original plate, a stronger coating can be formed by irradiating with light, heat or an electron beam and crosslinking. The above-mentioned coupling agent can be diluted with a water-alcohol or acetic acid water-alcohol mixture as necessary to prepare a treatment liquid. The concentration of the coupling agent in the treatment liquid is preferably 0.05 to 10.0% by mass. The treatment of the surface of the printing plate with a coupling agent is carried out by applying a treatment liquid containing the above-mentioned coupling agent to the surface of the printing plate before laser engraving or to the surface of the printing plate after laser engraving. The method of applying the coupling agent treatment liquid to the printing original plate is not particularly limited, and for example, a dipping method, a spray method, a roll coating method, a brush coating method, etc. can be applied. The coating temperature and the coating time are also not particularly limited, but it is preferably 5 to 60°C, and the treatment time is preferably 0.1 to 60 seconds. Furthermore, the treatment liquid layer formed on the surface of the printing original plate is preferably dried under heating, and the heating temperature is preferably 50 to 150°C.
[0059] As a preliminary step to treating the surface of the printing plate with a coupling agent, hydroxyl groups may be generated on the surface of the printing plate so that the coupling agent can be fixed at a high density. Specific methods include, for example, a method of irradiating the surface with light in the vacuum ultraviolet region having a wavelength of 200 nm or less, such as a xenon excimer lamp, or a method of exposing the surface to a high-energy atmosphere such as plasma.
[0060] The laminate of the present embodiment is suitable as a master plate for forming a relief image on a printing plate.Other uses include stamps, seals, design rolls for embossing, pattern forming materials for insulators, resistors, and conductor pastes used in electronic components, pattern forming materials for functional materials such as anti-reflection films for optical components, color filters, and (near) infrared absorbing filters, coating and pattern forming materials for alignment films, underlayers, light-emitting layers, electron transport layers, and sealant layers in the manufacture of display elements such as liquid crystal displays and organic electroluminescence displays, relief image forming materials for mold materials for ceramic products, relief image forming materials for displays such as advertisements and display boards, and masters and mother molds for various molded products.
[0061] (Protective film) The laminate of this embodiment has a configuration in which a protective film is laminated on a printing original plate. Examples of the protective film include, but are not limited to, polyester films such as polypropylene film, polyethylene film, polyethylene terephthalate, and polyethylene naphthalate; polyamide film; and the like. Among these, polyethylene terephthalate having a thickness in the range of 75 to 300 μm and being dimensionally stable is preferred. From the viewpoint of peelability, the protective film is preferably one in which a concave-convex pattern having a height of 2 μm or more is formed on the surface, including embossing.
[0062] (Physical properties of printing plate) <Storage modulus> In the laminate of this embodiment, the printing plate has a storage modulus G' at 140° C. of 5.00×10 4 Pa or more 1.00×10 6 It is preferable that the pressure is 0.1 Pa or less. The storage modulus G' of the printing plate is 5.00 x 10 4 Pa or more, the engraving quality during laser engraving is stabilized, and the engraving pressure is 1.00×10 6 By keeping the pressure drop at or below 1 Pa, the effect of improving engraving accuracy during laser engraving can be obtained. The storage modulus G' of the printing plate at 140°C is 8.00 x 10 4 Pa ~ 9.00 x 10 5 Pa, more preferably 2.00×10 5 Pa ~ 7.00 x 10 5 Pa is even more preferred. The storage modulus G' of the printing original plate can be controlled within the above-mentioned numerical range by adjusting the addition ratio of the organic compound (b) contained in the photosensitive resin composition. The storage modulus G' of the printing original plate can be measured using Discovery HR2 (product name, manufactured by TA Instruments Inc.), specifically, by the following method. It can also be measured by the method described in the examples below. In addition, the storage modulus G' at 140°C is 5.00 x 10 4 By having a storage modulus G' of 1.00 x 10 Pa or more, intramolecular motion is easily activated, and the processing efficiency with an ultrashort pulse laser can be improved. 6 By keeping the pressure at or below 1 Pa, it is possible to prevent the occurrence of defects such as cracks on the surface of the printing plate due to the impact of the generated plasma, and it is possible to maintain sufficient processing precision.
[0063] <How to measure storage modulus (G')> The storage modulus (G') of the printing original plate is measured using a dynamic viscoelasticity measuring device Discovery HR2 (trade name, manufactured by TA Instruments Inc.) according to the following procedure. The photosensitive resin composition layer is sandwiched between polyethylene terephthalate films having a total thickness of 135 μm, and laminated to a thickness of 2 mm. The laminate is irradiated with ultraviolet light from both sides (ultraviolet light irradiation cumulative dose: 4000 mJ / cm 2) is performed, and in this state, the polyethylene terephthalate films on both sides are removed, and the photosensitive resin composition layer is cut into a circle with a diameter of 8 mm and a thickness of 2 mm. The sample is set in the load-control type geometry of the dynamic viscoelasticity measuring device Discovery HR2, the effective measurement thickness is 1.9 mm, the initial strain is 0.1%, the measurement frequency is given in the range of 0.01 Hz to 15.915 Hz with a sine wave, the measurement temperature is measured from 20 ° C to 160 ° C in 10 ° C increments, and a master curve is created with a reference temperature of 20 ° C according to the application of the device by the temperature-time conversion side, and the storage modulus G' value at 140 ° C at 1000 Hz is read. This allows the storage modulus at 140 ° C to be measured.
[0064] <Melt flow rate (MFR)> In the laminate of this embodiment, the printing original plate preferably has a melt flow rate (MFR) of 0 (g / 10 min) or more and 20 (g / 10 min) or less. By making the MFR of the printing plate 0 (g / 10 min) or more, the printing plate can be uniformly converted into plasma when the printing plate is converted into plasma by laser irradiation, and the processing efficiency in the depth direction during processing can be improved. Also, by making the MFR 20 (g / 10 min) or less, sufficient durability against the heat generated when forming a concave-convex pattern with an ultrashort pulse laser beam can be ensured, and the thickness uniformity of the surface of the printing plate can be improved. The MFR of the printing plate precursor is more preferably from 0.1 to 10 (g / 10 min), and further preferably from 1 to 10 (g / 10 min). The MFR of the printing plate precursor can be controlled within the above-mentioned range by adjusting the compounding ratio of the thermoplastic elastomer. The MFR of the printing plate precursor can be measured by the method of ASTM D1238, specifically, by the method described in the examples below.
[0065] <Melt flow rate (MFR) measurement method> The MFR of the printing plate precursor is determined according to ASTM D1238, by measuring at a temperature of 150° C. and a load of 2.16 kg. The stability of the laser-engraved shape can be evaluated from the melt flow rate: if the MFR value is high, it can be determined that the engraved shape is more likely to melt due to the heat generated during laser engraving. The "MFR" of the printing original plate in the laminate of this embodiment is the result of UV irradiation (ultraviolet irradiation cumulative dose: 4000 mJ / cm2) on both sides of the photosensitive resin composition layer constituting the laminate. 2 ) The physical properties (melt flow rate) after
[0066] <Light transmittance> In the laminate of this embodiment, the printing original plate preferably has a light transmittance of 10% or more and 99.9% or less at the wavelength of the ultrashort pulsed laser light for forming the concave-convex pattern. High light transmittance allows the laser light to penetrate deeper, the photosensitive resin to be uniformly converted into plasma, and processing efficiency can be improved. On the other hand, if the light transmittance is too high, the absorption efficiency of the laser light decreases and the plasma phenomenon is less likely to occur, so the above numerical range is preferable. Specifically, when the light transmittance is 10% or more, the effect of improving the ablation processing efficiency can be obtained, and when the light transmittance is 99.9% or less, the effect of improving the ablation processing quality can be obtained. The light transmittance is more preferably 70 to 99.9%, even more preferably more than 75% and 99.9% or less, and even more preferably more than 95% and 99.9% or less. The light transmittance at the wavelength of the ultrashort pulsed laser light used to form the concave-convex pattern of the printing original plate can be controlled within the above-mentioned numerical range by blending an ultraviolet absorber, dye, or pigment. The light transmittance can be measured by a spectrophotometer. Specifically, it can be measured by the method described in the examples below.
[0067] <Method of measuring light transmittance> The light transmittance (%) at the wavelength of the laser light is a value measured using an ultraviolet / visible / near-infrared spectrophotometer "V-750" (product name, manufactured by JASCO Corporation). The measurement stage used is FLH-467 (product name, manufactured by JASCO Corporation), and the software used is SpectraManager (product name, manufactured by JASCO Corporation). Measurements are performed with a bandwidth of 2 nm, a scanning speed of 400 nm / min, and a data acquisition interval of 2 nm. As a sample, the protective film and support are peeled off and the total thickness of the printing original plate is measured at 1 mm.
[0068] [Method of manufacturing a printing plate] The method for producing a printing plate of this embodiment includes a laser engraving step of forming a concave-convex pattern on the surface of the printing blank of the laminate of this embodiment described above by using an ultrashort pulsed laser beam. The above-mentioned "ultrashort pulsed laser light" refers to electromagnetic pulsed laser light on the time order of several hundred picoseconds or less, and includes light on the time order of femtoseconds to attoseconds. In the laser engraving process, the surface of the printing original plate is irradiated with ultrashort pulsed laser light, and the resin in the areas irradiated with the laser light is removed, thereby forming a desired concave-convex pattern. In the method for producing a printing plate according to the present embodiment, it is preferable to use a laser engraving device capable of forming fine patterns using a laser having a lower average output as a light source compared to a continuous wave laser having a gigawatt-class output, thereby achieving cost reduction. In addition, ultrashort pulsed laser light has a large maximum peak power per pulse, which acts directly on the covalent bonds between the molecules of the compound that makes up the printing plate, ionizing only specific atoms and gasifying them with the plasma phenomenon, which then disperses them. This results in high processing efficiency and fewer steps, which also improves the production efficiency of printing plates.
[0069] In the method for producing a printing plate according to the present embodiment, the printing master plate has a storage modulus G′ of 5.00×10 at 140° C. 4 Pa or more 1.00×10 6 It is preferable that the pressure is 0.1 Pa or less. The storage modulus G' of the printing plate is 5.00 x 10 4 Pa or more, the engraving quality during laser engraving is stabilized, and the engraving pressure is 1.00×10 6 By keeping the pressure drop at or below 1 Pa, the effect of improving engraving accuracy during laser engraving can be obtained. The storage modulus G' of the printing plate at 140°C is 8.00 x 10 4 Pa ~ 9.00 x 10 5 Pa, more preferably 2.00×10 5 Pa ~ 7.00 x 10 5 Pa is even more preferred. When the printing original plate is a photosensitive resin composition, the storage modulus G' of the printing original plate can be controlled within the above-mentioned numerical range by adjusting the addition ratio of the organic compound (b) contained in the photosensitive resin composition. The storage modulus G' of the printing plate precursor can be measured using Discovery HR2 (trade name, manufactured by TA Instruments Inc.) by the method described in the Examples below. In addition, the storage modulus G' at 140°C is 5.00 x 10 4 By having a storage modulus G' of 1.00 x 10 Pa or more, intramolecular motion is easily activated, and the processing efficiency with an ultrashort pulse laser can be improved. 6 By keeping the pressure at or below 1 Pa, it is possible to prevent the occurrence of defects such as cracks on the surface of the printing plate due to the impact of the generated plasma, and it is possible to maintain sufficient processing precision.
[0070] In the printing plate manufacturing method of this embodiment, the focus depth of the ultrashort pulsed laser light in the engraving step is preferably 25 μm or more and 700 μm or less from the surface of the printing original plate. In other words, it is preferable that at least a portion of the printing original plate having a thickness of 25 μm or more and 700 μm or less from the surface of the printing original plate is made of a cured resin having light transmittance in the near-infrared region. In order to ensure sufficient mechanical strength, the surface portion of the printing original plate is preferably made of a cured resin having light transmittance in the ultraviolet region. In the case where the printing original plate has a modified layer on its surface, the surface portion means the portion excluding the modified layer.
[0071] Furthermore, the printing original plate preferably has a light transmittance of 10% or more and 99.9% or less, more preferably 70% or more and 99.9% or less, even more preferably 75% or more and 99.9% or less, even more preferably more than 75% and 99.9% or less, and even more preferably more than 95% and 99.9% or less, at the wavelength of the ultrashort pulsed laser light used in the laser engraving process.
[0072] The light transmittance is a value relative to the wavelength of ultrashort pulsed laser light used in the engraving process for the printing plate constituting the laminate of this embodiment. Specifically, the light transmittance of the printing original plate can be measured by using a cured resin material designed to a thickness equivalent to that of the printing original plate, and employing a light transmittance method in an ultraviolet-visible-near infrared spectrophotometer. When the light transmittance of the printing original plate at the wavelength of the ultrashort pulsed laser light used in the engraving process is in the range of 10% or more and 99.9% or less, laser engraving in the depth direction is performed satisfactorily and it is preferable from the viewpoint that a laser with a low average output can be used as the light source.
[0073] In the method for producing a printing plate of this embodiment, an ultrashort pulsed laser is used, and the ultrashort pulsed laser used in this production method is a pulsed ultraviolet and near-infrared laser having an oscillation wavelength in the wavelength region from the near-ultraviolet region through the visible light region to the near-infrared region. The near-infrared region is defined as the region with wavelengths of 700 nm or more and 3 μm or less. The visible light region is defined as the region with wavelengths of 320 nm or more and 700 nm or less. The ultraviolet region is defined as the region with wavelengths of 100 nm or more and 400 nm or less. In the printing plate manufacturing method of this embodiment, the oscillation wavelength of the ultrashort pulsed laser light used in the laser engraving step is preferably 300 nm or more and 1.5 μm or less, more preferably 300 nm or more and 700 nm or less, even more preferably 400 nm or more and 700 nm or less, and even more preferably 450 nm or more and less than 700 nm. When the oscillation wavelength of the laser light in the engraving process is 300 nm or more, the ablation processing efficiency can be improved, and when it is 1.5 μm or less, the ablation processing quality can be improved.
[0074] The type of near-infrared laser is not particularly limited, but examples include the fundamental wave of a semiconductor laser pumped solid-state laser or a lamp pumped solid-state laser, a second harmonic wave or a third harmonic wave obtained by wavelength conversion, a semiconductor laser, a fiber laser, and the like. In particular, from the viewpoints of oscillation stability and ease of handling, semiconductor laser-pumped solid-state lasers and fiber lasers are preferred. Examples of solid-state lasers include, but are not limited to, an alexandrite laser, a titanium sapphire laser, a Cr:LiSAF laser, an F-Center laser, a Co:MgF2 laser, a Nd:YAG laser, a Nd:YLF laser, a Nd:YVO4 laser, an Er:glass laser, a Ho:YAG laser, a Ho:YSGG laser, a Tm:YAG laser, and an Er:YAG laser. In the case of semiconductor laser-pumped solid-state lasers, there are two types of pumping methods: side pumping and end pumping. In order to obtain an excellent beam shape, the end pumping method is more preferable.
[0075] The laser used in the method for producing a printing plate of this embodiment is preferably a pulsed near-infrared laser, and the repetition frequency is preferably 20 kHz to 500 MHz, more preferably 100 kHz to 200 MHz, and even more preferably 500 kHz to 100 MHz. By setting the oscillation frequency in the range of 20 kHz to 500 MHz, it is possible to perform engraving by scanning the laser beam at high speed, which is preferable from the viewpoint of shortening the time required for the engraving process.
[0076] The pulse width of the ultrashort pulsed laser used in the method for producing a printing plate of this embodiment is preferably in the range of 1 femtosecond to 200 nanoseconds, more preferably 10 femtoseconds to 100 nanoseconds, and even more preferably 10 femtoseconds to 30 nanoseconds. By making the pulse width 1 femtosecond or more and 200 nanoseconds or less, a high peak output can be obtained even if the average output of the laser is small, and a large amount of energy can be input in an extremely short period of time. This makes it easy to engrave the printing plate, has the effect of suppressing the effects of heat, and results in an excellent pattern shape. A preferred method for obtaining femtosecond or picosecond pulses is to use a mode-locking technique, and a preferred method for obtaining short pulses with high peak output is to use a laser with a Q switch.
[0077] In the method for producing a printing plate of this embodiment, the overlap rate between successive pulses of the ultrashort pulsed laser light used in the laser engraving step is preferably 50% or more and 99% or less. The overlap rate of the laser light can be calculated by the overlapping area ratio or overlapping diameter ratio of the laser light irradiated onto the printing original plate for each successive pulse. A laser beam overlap rate of 50% or more in the engraving process ensures sufficient laser irradiation intensity, while a laser beam overlap rate of 99% or less ensures a practically sufficient engraving speed. The overlap rate of the laser light in the engraving step is more preferably from 70.0 to 99.0%, and even more preferably from 85.0 to 99.0%.
[0078] In the method for producing a printing plate of this embodiment, the average output of the ultrashort pulsed laser beam used in the engraving step is preferably 0.01 W or more and less than 1000 W. More preferably, it is from 0.05 W to 800 W, even more preferably from 0.1 W to 100 W, and even more preferably from 0.8 W to 500 W. By setting the average output of the ultrashort pulsed laser beam in the engraving process to 0.01 W or more and less than 1000 W, the printing plate can be easily engraved and the edge shape of the resulting relief pattern can be made clear. In addition, the effect of heat is small, and a relief pattern with a width approximately equal to the laser beam diameter can be obtained without excessive melting or removal.
[0079] The power per pulse of the ultrashort pulsed laser light used in the engraving step of the printing plate manufacturing method of this embodiment is preferably 20 kW or more and 10 GW or less. A more preferred range is 100 kMW or more and 5 GW or less, and even more preferably 1 MW or more and 1 GW or less. A power per pulse of 20 kW or more is preferable from the viewpoints that the printing master plate can be easily laser-engraved and the edge shape of the obtained pattern is clear. Moreover, a power per pulse of 10 GW or less is preferable from the viewpoint of being less affected by heat, not being excessively melted or removed, and being able to obtain a concave pattern with a width approximately equal to the laser beam diameter. The power per pulse (unit: W) is defined as the average output (unit: W) divided by the repetition frequency (unit: pulse / sec), which is then divided by the pulse width (time width of one pulse, unit: sec). The higher the power per pulse defined above, the higher the peak output.
[0080] In the method for producing a printing plate of this embodiment, the energy per pulse of the ultrashort pulsed laser light used in the laser engraving step is preferably from 1 μJ to 100 kJ. The energy per pulse of laser light, measured in J, is the average output (unit: W) divided by the repetition frequency (unit: pulses / second). When the energy per pulse of the laser beam is 1 μJ or more, the original printing plate can be easily laser-engraved, and this is preferable from the viewpoint that the edge shape of the obtained pattern becomes clear. A laser power of 100 kJ or less is preferable in that it reduces the effect of heat, prevents excessive melting or removal, and enables a concave pattern having a width approximately equal to the laser beam diameter to be obtained. The energy per pulse of the laser light is more preferably from 1 μJ to 1 kJ, and further preferably from 1 μJ to 100 μJ.
[0081] In the method for manufacturing a printing plate of this embodiment, in order to accurately form a fine pattern, for example a fine concave-convex pattern having a width of 1 μm or more and less than 200 μm and a depth of 1 μm or more and less than 1000 μm, it is preferable to focus the laser beam output from an ultrashort pulse oscillation laser to a diameter of 1 μm or more and less than 20 μm, and to irradiate the focused beam onto the surface of the printing original plate. The depth of the printing original plate engraved with one pulse of the ultrashort pulsed laser light used in the engraving step is preferably 1 μm or more and 100 μm or less. The depth of the printing original plate engraved with one pulse is preferably in the range of 1 μm or more and 30 μm or less from the viewpoints of being able to form a relief pattern with dimensions approximately equal to the diameter of the laser beam and being able to deeply engrave the same location with multiple pulses by using a pulsed near-infrared laser with a high repetition frequency. In order to focus a laser beam, it is preferable to use lenses including a diffraction grating type, homogenizer type, and field mapping type lens, as well as a fiber core type beam shaper, a collimating lens, and a telecentric lens.
[0082] In the laser engraving step of the printing plate manufacturing method of this embodiment, it is preferable to use an fθ lens with large dimensions, particularly when the laser beam is scanned in a single or two axial directions over a relatively wide width or area using a galvanometer mirror. In the method for producing a printing plate of this embodiment, the lens used in the laser engraving step preferably has a numerical aperture (NA) of 0.01 or more and 0.100 or less. A lens numerical aperture of 0.01 or more allows easy laser engraving of the printing plate, and also allows the laser beam spot diameter to be reduced, which is preferable from the viewpoint of obtaining fine shapes. By using a lens with a numerical aperture of 0.100 or less, the focal depth of the laser on the printing original plate can be easily increased, and the edge shape of the obtained pattern becomes clear, which is preferable. The numerical aperture of the lens is more preferably 0.02 or more and 0.900 or less, and further preferably 0.03 or more and 0.800 or less. When the material to be irradiated with laser light is a cured resin, a concave-convex pattern having a width approximately equal to the diameter of the irradiated beam can be formed by using a laser with a low average output. In order to achieve ablation processing, the pulsed laser light is preferably a multi-mode laser light, i.e., a TEM00 mode laser light before focusing. Furthermore, the M2 value, which is an index representing the quality of the transverse mode of the laser, is preferably 1 or more and 2 or less. A more preferable range is 1 or more and 1.8 or less, and an even more preferable range is 1 or more and 1.5 or less.
[0083] In the laser engraving step in the printing plate manufacturing method of this embodiment, a laser device is generally operated using a computer to input the image to be formed as digital data, thereby producing a relief image on the printing plate master. In the method for producing a printing plate according to the present embodiment, a fine pattern is preferably formed using a near-ultraviolet laser beam to a near-infrared laser beam as an ultrashort pulsed laser beam. However, when a coarser pattern, for example, a pattern having a width exceeding 20 μm, is to be present in the same printing plate, an engraving step using an infrared laser can be further carried out as the laser engraving step. In this case, the infrared laser may be either continuous oscillation or pulse oscillation, and it is preferable to laser engrave the surface of the printing plate with a beam diameter of 15 μm or more and less than 100 μm. In order to perform the engraving process in a short time, engraving can also be performed using an infrared laser having an oscillation wavelength of 5 μm or more and 20 μm or less. A particularly preferred specific example of an infrared laser is a carbon dioxide laser. The oscillation mode of the carbon dioxide laser may be continuous oscillation or pulse oscillation. In addition, it is possible to form a coarse uneven pattern having a width of more than 15 μm and a depth of 100 μm or more by concentrating the laser beam diameter output from the infrared laser to 15 μm or more and less than 100 μm.
[0084] In the method for producing a printing plate of this embodiment, the number of pulsed laser beams used in the laser engraving step is preferably at least one. By using multiple laser beams, the engraving speed can be significantly increased. The engraving with the ultrashort pulsed laser beam and the engraving with the infrared laser may be carried out simultaneously or separately, but from the viewpoint of shortening the time required for engraving, it is preferable to carry them out simultaneously. However, this does not apply when the laser engraving device uses a different laser beam scanning method, for example, when a pulsed near-infrared laser scans using a galvanometer mirror, whereas an infrared laser engraves without using a galvanometer mirror.
[0085] In the laser engraving step in the printing plate manufacturing method of this embodiment, from the viewpoint of laser engraving speed, it is preferable to irradiate the laser light while rotating the cylinder in the circumferential direction with a fixed longitudinal axis in a state in which a sheet-like printing blank is wrapped and fixed on the surface of the cylinder or a cylindrical printing blank is attached to the cylinder. This method makes it possible to perform laser engraving while rotating the cylinder at high speed. From the viewpoint of ensuring positional accuracy in laser engraving, the method of irradiating the laser light is preferably a method in which the laser beam is scanned in the longitudinal direction of the cylinder while rotating the cylinder, or a method in which a galvanometer mirror is used to scan the cylinder in the longitudinal direction. The engraving apparatus used for laser engraving is preferably an apparatus equipped with a cylinder and capable of engraving while rotating, which is particularly preferred when producing cylindrical printing plates.
[0086] In the printing plate manufacturing method of this embodiment, the laser used as the ultrashort pulse oscillation laser light in the laser engraving step has a high oscillation frequency, so that a scanning method using a galvanometer mirror is preferably used as a laser beam scanning method. When a laser beam is scanned in the axial direction of the cylinder using a galvanometer mirror, the cylinder is rotated once to laser engrave a pattern for one revolution according to image data divided in the axial direction of the cylinder, and then the galvanometer mirror is moved in the axial direction of the cylinder or the cylinder is moved in the axial direction. By repeating this series of steps, it is possible to laser engrave a pattern corresponding to all of the image data.
[0087] The laser engraving apparatus used in the laser engraving step in the printing plate manufacturing method of this embodiment preferably has a pulsed near-infrared laser, a galvanometer mirror for scanning the laser beam in the axial direction of the cylinder, a focusing lens for focusing the laser beam, and an optical shutter or a mechanical shutter, and also has a mechanism for holding the axial direction of the cylinder, a mechanism for rotating the held cylinder in the circumferential direction, and a mechanism for moving the galvanometer mirror in the axial direction of the cylinder or a mechanism for moving the cylinder in its axial direction. Furthermore, it is preferable that the laser engraving device is a device having a continuous wave infrared laser and an optical shutter, or a pulsed wave infrared laser and an optical shutter or a mechanical shutter, a focusing lens for focusing the laser beam, and a mechanism for moving the laser beam in the longitudinal direction of the cylinder, or a mechanism for moving the cylinder in its longitudinal direction. A galvanometer mirror is an optical component that scans a laser beam in a single or two-axis direction under computer control, and is also called a galvanometer scanner. There are two types of mirror, a moving coil type and a moving magnet type, depending on the driving method of the mirror part, and they can be used depending on the oscillation frequency of the laser used, the scanning accuracy, and the scanning area. It is preferable to use an acousto-optical modulator (AO modulator) as an optical shutter.
[0088] The laser engraving step in the method for producing a printing plate of this embodiment is carried out under an oxygen-containing gas, generally in the presence of air or under an air stream, but can also be carried out under carbon dioxide gas or nitrogen gas. If gas or fine powdery debris is generated during laser engraving, it is effective to blow air or an inert gas onto the engraving to remove it. After engraving, any powdery or liquid material that is generated in small amounts on the relief surface may be removed by known methods, such as washing it off with water containing a solvent or surfactant, irradiating it with a water-based cleaner using a high-pressure spray, or irradiating it with high-pressure steam.
[0089] In the laser engraving step in the method for producing a printing plate according to the present embodiment, after engraving to form a fine concave-convex pattern by irradiating a laser beam, a step of removing powdery or viscous liquid residue remaining on the surface of the printing plate may be carried out, and then a post-exposure step of irradiating the surface of the printing plate with light having a wavelength of 200 nm to 450 nm may be carried out. By carrying out this post-exposure, tackiness on the surface of the printing plate can be effectively removed. The post-exposure may be carried out in any environment, such as in the air, in an inert gas atmosphere, or in water. In particular, when the material of the printing plate contains a hydrogen abstraction type photopolymerization initiator, the effect of removing tackiness by the post-exposure is high. Furthermore, the surface of the printing plate may be treated with a treatment liquid containing a hydrogen abstraction type photopolymerization initiator before the post-exposure step, and the post-exposure step may be carried out. The post-exposure step may also be carried out in a state where the printing plate is immersed in a treatment liquid containing a hydrogen abstraction type photopolymerization initiator. EXAMPLES
[0090] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples and comparative examples. The physical properties used in the following examples and comparative examples are shown below.
[0091] [Melt flow rate (MFR)] The melt flow rate (g / 10 min) of the printing plate was measured in accordance with ASTM D1238 at a temperature of 150° C. and a load of 2.16 kg. The stability of the laser-engraved shape was evaluated based on the melt flow rate. It was determined that if the MFR value is large, the engraved shape is more likely to melt due to the heat generated during laser engraving. In addition, in Tables 1 and 2, "MFR" refers to the amount of ultraviolet radiation applied to both sides of the photosensitive resin composition (ultraviolet radiation cumulative dose: 4000 mJ / cm 2 ) The physical properties (melt flow rate) after
[0092] [Light transmittance at laser wavelength] The light transmittance (%) of the printing plate at the laser wavelength was measured using a UV / Vis / Near-infrared spectrophotometer "V-750" (product name, manufactured by JASCO Corporation). The measurement wavelengths were 1064 nm, 515 nm, and 343 nm. The measurement stage used was FLH-467 (product name, manufactured by JASCO Corporation) and the software was SpectraManager (product name, manufactured by JASCO Corporation). Measurements were performed with a bandwidth of 2 nm, a scanning speed of 400 nm / min, and a data acquisition interval of 2 nm. The measurement sample was a printing master plate with the protective film and support peeled off, with the total thickness of the sample being 1 mm.
[0093] [Storage modulus (G')] The storage modulus (G') of the printing original plate was measured using a dynamic viscoelasticity measuring device Discovery HR2 (trade name, manufactured by TA Instruments Inc.) according to the following procedure. The photosensitive resin composition layer was sandwiched between polyethylene terephthalate films having a total thickness of 135 μm, and laminated to a thickness of 2 mm, thereby obtaining a photosensitive resin composition structure of PET film / photosensitive resin composition layer / PET film. The photosensitive resin composition structure was irradiated with ultraviolet light from both sides (ultraviolet light irradiation cumulative dose: 4000 mJ / cm 2 ) was performed, and in this state, the polyethylene terephthalate films on both sides were removed, and the photosensitive resin composition layer was cut into a circle with a diameter of 8 mm and a thickness of 2 mm to be used as a measurement sample. The measurement sample was set in the load-control type geometry of a dynamic viscoelasticity measuring device Discovery HR2. The effective measurement thickness was 1.9 mm, the initial strain was 0.1%, the measurement frequency was given in the range of 0.01 Hz to 15.915 Hz with a sine wave, and the measurement temperature was measured in 10°C increments from 20°C to 160°C. According to the application of the dynamic viscoelasticity measuring device, a master curve was created with a reference temperature of 20°C on the temperature-time conversion side, and the storage modulus G' value at 140°C at 1000Hz was read.
[0094] [Production of Laminate before Exposure] (Production Example 1) <Photosensitive resin composition> Photosensitive resin composition 1 used for printing original plate 1 was prepared as follows. The mixture consisted of 55 parts by mass of a thermoplastic elastomer which is a block copolymer of styrene and butadiene (Kraton Polymer Japan, product name "KX-405", Mn 100,000, styrene content 24% by mass), 24 parts by mass of liquid paraffin which is a plasticizer (MORESCO, product name "Sumoil P350P", Mn 483), 13 parts by mass of liquid rubber elastomer which is a liquid polybutadiene polymer which is a plasticizer (Kuraray, product name "LBR-352", Mn 6200), and 1,9-nonanemethylene diacrylate which is a photopolymerizable monomer (Kyoeisha Chemical Co., Ltd.). Photosensitive resin composition 1, which is the raw material for the printing plate, was obtained by uniformly kneading 6 parts by mass of NMDA (product name), 2 parts by mass of 2,2-dimethoxy-1,2-diphenylethan-1-one (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a photopolymerization initiator, and 1 part by mass of 2,6-di-t-butyl-p-cresol as a thermal polymerization inhibitor, in a kneader heated to 180°C.
[0095] <Support> Furthermore, a polyethylene terephthalate film support having a total thickness of 135 μm and having a urethane-based adhesive layer was prepared as follows. First, a polyethylene terephthalate film support having a thickness of 125 μm was prepared as follows. 93 g of ethylene glycol, 374 g of neopentyl glycol, and 382 g of phthalic acid were subjected to a condensation reaction in an air atmosphere at a reaction temperature of 180°C under a reduced pressure of 1330 Pa for 6 hours, after which 125 g of 4,4-diphenylenediisocyanate was added and the mixture was further reacted at 80°C for 5 hours to obtain a resin. This resin was made into a 10% aqueous solution, which was then applied onto the polyethylene terephthalate film having a thickness of 125 μm, and after coating, the film was biaxially stretched to obtain a polyethylene terephthalate film having an undercoat layer. The thickness of the undercoat layer was 0.05 μm. Next, a urethane-based adhesive layer prepared as described below was applied to the polyethylene terephthalate film support having the undercoat layer. 624 g of neopentyl glycol, 93 g of ethylene glycol, 485 g of sebacic acid, and 382 g of isophthalic acid were subjected to a condensation reaction in an air atmosphere at a reaction temperature of 180° C. under a reduced pressure of 1330 Pa for 6 hours, after which 87 g of trimethylene diisocyanate was added and the reaction was continued for an additional 5 hours to obtain a polyol. 1 part by mass of xylylene diisocyanate was added to 15 parts by mass of this polyol, and dissolved in ethyl acetate to obtain a homogeneous solution. This solution is a urethane-based adhesive solution. This solution was applied to a polyethylene terephthalate film using a knife coater, and dried at 80°C for 3 minutes to form an adhesive layer with a thickness of 10 μm. As a result, a polyethylene terephthalate film support with a total thickness of 135 μm was obtained.
[0096] <Laminate before exposure> Next, using a hot press at 120°C, the above photosensitive resin composition 1 was sandwiched between a 135 μm thick polyethylene terephthalate film support (support film) having an adhesive layer and a polyethylene terephthalate film (surface protection film), and molded to an overall thickness of 3 mm to obtain laminate 1 before exposure.
[0097] (Production Example 2) Photosensitive resin composition 2 used for printing original plate 2 was prepared as follows. 81 parts by mass of thermoplastic elastomer "D-1161" (manufactured by Kraton Polymer Japan, product name, Mn 180,000, styrene content 15% by mass), which is a block copolymer of styrene and isoprene, 10 parts by mass of liquid polybutadiene "B2000" (manufactured by Nippon Soda, product name), which is a plasticizer, 5 parts by mass of 1,9-nonanmethylene diacrylate, which is a photopolymerizable monomer, 3 parts by mass of 2,2-dimethoxy-2-phenylacetophenone, which is a photopolymerization initiator, and 1 part by mass of 2,6-di-t-butyl-p-cresol, which is a thermal polymerization inhibitor, were uniformly kneaded using a kneader heated to 160°C to obtain photosensitive resin composition 2, which is the raw material for the printing plate. Next, similarly to the above (Manufacturing Example 1), using a hot press at 120°C, the above photosensitive resin composition 2 was sandwiched between a 135 μm thick polyethylene terephthalate film support (support film) having an adhesive layer and a polyethylene terephthalate film (surface protection film), and molded to a total thickness of 3 mm, thereby obtaining a laminate 2 before exposure.
[0098] (Production Example 3) A photosensitive resin composition 3 used for the printing original plate 3 was prepared as follows. 67 parts by mass of thermoplastic elastomer "D-1161" (manufactured by Kraton Polymer Japan, product name, Mn 180,000, styrene content 15% by mass), which is a block copolymer of styrene and isoprene, 15 parts by mass of liquid polybutadiene "B2000" (manufactured by Nippon Soda, product name), which is a plasticizer, 4 parts by mass of 1,9-nonanmethylene diacrylate, which is a photopolymerizable monomer, 3 parts by mass of 2,2-dimethoxy-2-phenylacetophenone, which is a photopolymerization initiator, and 1 part by mass of 2,6-di-t-butyl-p-cresol, which is a thermal polymerization inhibitor, were uniformly kneaded using a kneader heated to 160°C to obtain photosensitive resin composition 2, which is the raw material for the printing plate. Next, similarly to the above (Manufacturing Example 1), using a hot press at 120°C, the above photosensitive resin composition 3 was sandwiched between a 135 μm thick polyethylene terephthalate film support (support film) having an adhesive layer and a polyethylene terephthalate film (surface protection film), and molded to a total thickness of 3 mm, thereby obtaining a laminate 3 before exposure.
[0099] (Production Example 4) Photosensitive resin composition 4 used for printing original plate 4 was prepared as follows. 85 parts by mass of a thermoplastic elastomer which is a block copolymer of styrene and butadiene (manufactured by Kraton Polymer Japan, product name "KX-405", Mn 100,000, styrene content 24% by mass), 10 parts by mass of a liquid rubber elastomer which is a plasticizer, a liquid polybutadiene polymer (manufactured by Kuraray, product name "LBR-352", Mn 6200), 3 parts by mass of 1,9-nonanemethylene diacrylate which is a photopolymerizable monomer (manufactured by Kyoeisha Chemical, product name NMDA), and 1 part by mass of 2,6-di-t-butyl-p-cresol which is a thermal polymerization inhibitor were uniformly kneaded using a kneader heated to 180°C to obtain photosensitive resin composition 4 which is the raw material for the printing plate. Next, similarly to the above (Manufacturing Example 1), using a hot press at 120°C, the above resin composition 4 was sandwiched between a 135 μm thick polyethylene terephthalate film support (support film) having an adhesive layer and a polyethylene terephthalate film (surface protection film), and molded to an overall thickness of 3 mm to obtain a laminate 4 before exposure.
[0100] (Production Example 5) Photosensitive resin composition 5 used in printing original plate 5 was prepared as follows. 77 parts by mass of thermoplastic elastomer "D-1161" (manufactured by Kraton Polymer Japan, product name, Mn 180,000, styrene content 15% by mass), which is a block copolymer of styrene and isoprene, 5 parts by mass of liquid polybutadiene "B2000" (manufactured by Nippon Soda, product name), which is a plasticizer, 3 parts by mass of 1,9-nonanmethylene diacrylate, which is a photopolymerizable monomer, 10 parts by mass of 2,2-dimethoxy-2-phenylacetophenone, which is a photopolymerization initiator, and 5 parts by mass of 2,6-di-t-butyl-p-cresol, which is a thermal polymerization inhibitor, were uniformly kneaded using a kneader heated to 160°C to obtain photosensitive resin composition 5, which is the raw material for the printing plate. Next, similarly to the above (Manufacturing Example 1), using a hot press at 120°C, the above photosensitive resin composition 5 was sandwiched between a 135 μm thick polyethylene terephthalate film support (support film) having an adhesive layer and a polyethylene terephthalate film (surface protection film), and molded to an overall thickness of 3 mm, thereby obtaining a laminate 5 before exposure.
[0101] (Production Example 6) A photosensitive resin composition 6 used for the printing original plate 6 was prepared as follows. The mixture was mixed with 60 parts by mass of a thermoplastic elastomer which is a block copolymer of styrene and butadiene (Kraton Polymer Japan, product name "KX-405", Mn 100,000, styrene content 24% by mass), 24 parts by mass of liquid paraffin which is a plasticizer (MORESCO, product name "Sumoil P350P", Mn 483), 5 parts by mass of liquid rubber elastomer which is a liquid polybutadiene polymer which is a plasticizer (Kuraray, product name "LBR-352", Mn 6200), and 1,9-nonanemethylene diacrylate which is a photopolymerizable monomer (Kyoeisha Chemical, product name " ... Photosensitive resin composition 6, which is the raw material for the printing plate, was obtained by uniformly kneading 1 part by mass of NMDA (product name), 5 parts by mass of 2,2-dimethoxy-1,2-diphenylethan-1-one as a photopolymerization initiator, and 1 part by mass of 2,6-di-t-butyl-p-cresol as a thermal polymerization inhibitor in a kneader heated to 180°C. Next, similarly to the above (Manufacturing Example 1), using a hot press at 120°C, the above photosensitive resin composition 6 was sandwiched between a 135 μm thick polyethylene terephthalate film support (support film) having an adhesive layer and a polyethylene terephthalate film (surface protection film), and molded to a total thickness of 3 mm to obtain a laminate 6 before exposure.
[0102] (Production Example 7) Photosensitive resin composition 7 used for printing original plate 7 was prepared as follows. The mixture consisted of 55 parts by mass of a thermoplastic elastomer which is a block copolymer of styrene and butadiene (Kraton Polymer Japan, product name "KX-405", Mn 100,000, styrene content 24% by mass), 24 parts by mass of liquid paraffin which is a plasticizer (MORESCO, product name "Sumoil P350P", Mn 483), 13 parts by mass of a mixture of liquid rubber elastomer filled with carbon black (Kuraray, product name "LBR-352", Mn 6200) (90.5% by mass rubber, 9.5% by mass carbon black), and 1,9-nonanemethylene diacrylate which is a photopolymerizable monomer (Kyoeisha Chemical Co., Ltd.). Photosensitive resin composition 7, which is a raw material for the printing plate blank, was obtained by uniformly kneading 5 parts by mass of 2,2-dimethoxy-1,2-diphenylethan-1-one (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a photopolymerization initiator, 2 parts by mass of 2,6-di-t-butyl-p-cresol as a thermal polymerization inhibitor, and 1 part by mass of dye (Valifast Yellow 3150 (manufactured by Orient Chemical Industries, Ltd., product name)) using a kneader heated to 180°C. Next, similarly to the above (Manufacturing Example 1), using a hot press at 120°C, the above photosensitive resin composition 7 was sandwiched between a 135 μm thick polyethylene terephthalate film support (support film) having an adhesive layer and a polyethylene terephthalate film (surface protection film), and molded to a total thickness of 3 mm to obtain laminate 7 before exposure.
[0103] Example 1-1 (Laminate having a printing plate) A laminate including a printing master was prepared. First, a laminate provided with a printing original plate 1 was produced from the "laminate 1 before exposure" obtained in the above (Production Example 1). After exposure, the photosensitive resin composition layer 1 constituting the "laminate 1 before exposure" becomes the original printing plate 1 by peeling off the surface protective film. As an exposure device, an AFP-1321EHQ platemaking machine (trade name, manufactured by Asahi Kasei Corporation) equipped with an 80 W ultraviolet fluorescent lamp having a central wavelength region of 370 nm was used. This platemaking machine has a direct light irradiation intensity of 12.0 mW / cm, measured using a UV-35 filter (manufactured by Oak Seisakusho, product name) of an ultraviolet meter UV-MO2 (manufactured by Oak Seisakusho, product name). 2 , and it was confirmed that. Next, the "pre-exposed laminate 1" obtained in (Production Example 1) was exposed to light from the support side in the atmosphere using the light source of the plate making machine at an exposure dose of 500 mJ / cm. 2 , light intensity 4000mJ / cm from the surface protection film side 2 This gave a 20 cm square sheet-like laminate having a structure of support / printing original plate 1 / surface protection film. The above exposure dose was calculated using a UV-MO2 UV-35 filter (trade name, manufactured by Oak Seisakusho). In this example, the MFR of the photosensitive resin composition 1 having a support and a surface protection film on the top and bottom surfaces after exposure was 1.0 g / 10 min, which was less than half of the MFR before exposure, and therefore it was confirmed that the composition had cured. The storage modulus (G') was 1.00 x 10 5 Pa, the laser light transmittance at the laser wavelength (1064 nm) was 95%, the light transmittance at the laser wavelength (515 nm) was 90%, and the light transmittance at the laser wavelength (343 nm) was 23%. The physical properties of the printing plate are shown in the table below.
[0104] In the table, "full exposure" means that the exposure amount is at least 1 mJ / cm from the surface protection film side or the support film side of the laminate. 2 This means that the subject is exposed to the above amount of chemical radiation. In the table, "hardened" means that the MFR of the printing plate master has changed. The above points apply to the following Examples and Comparative Examples.
[0105] [Example 1-2] (Print version) Next, the printing plate 1 of the "laminate having the printing plate 1" prepared in the above-mentioned [Example 1-1], with the surface protective film removed, was subjected to laser engraving using the following ultrashort pulsed laser light to obtain a printing plate. Laser engraving of fine patterns was performed using an end-pumped semiconductor laser-excited Q-switched solid-state laser, a YAG laser with a fundamental wave of 1064 nm, “IceFyre 1064-50” (trademark, manufactured by Spectra-Physics), focusing the beam diameter to 28 μm with a lens. The laser repetition rate was 10 MHz, the pulse width was 0.1 picoseconds, the average output was 100 W, the overlap ratio was 95%, the lens NA was 0.037, the focus depth was 0.25 mm, and the energy per pulse was 20 μJ. The laser beam was fixed, the sample to be engraved (a sheet-shaped printing plate) was fixed on the XY stage, and the XY stage was moved to form a checkerboard pattern consisting of multiple concave-convex patterns. The M2 value, which indicates the quality of the beam, was less than 1.8. The output light passed through an 8x beam expander, and a focusing lens with an f-number of 100 mm was used. The printing master was fixed on the XYZ stage with the upper support film in contact with the lower stage, and the position was controlled so that the laser focus was on the inside of the printing master. A line-shaped uneven pattern was formed to engrave a checkerboard pattern as the laser engraving pattern. The area in which the line-shaped uneven pattern was formed was 3 mm x 100 mm. In the above region, a concave-convex pattern was formed in a line shape with a width of 145 μm in the vertical direction and a length of 100 mm in the horizontal direction at a pitch of 145 μm. Next, a concave-convex pattern was formed in a line shape with a width of 145 μm and a length of 100 mm at a pitch of 145 μm by shifting the pattern by 145 μm in the vertical and horizontal directions. This resulted in the formation of a pattern 1 with 20 lines in each direction. Next, a checkered pattern was engraved in an area shifted 100 mm in parallel from the pattern 1. A linear uneven pattern was formed with a pitch of 65 μm, a width of 65 μm in the vertical direction, and a length of 100 mm in the horizontal direction. Next, a linear uneven pattern was formed with a pitch of 65 μm, shifted by 65 μm in each of the vertical and horizontal directions, and a width of 65 μm in the vertical direction and a length of 100 mm in the horizontal direction. This formed pattern 2 with 46 lines vertically and horizontally. The XY stage, driven by a stepping motor, was moved at a speed of 1250 mm / sec. The resulting line-shaped concave-convex pattern 1 had a depth of 480 μm and the pattern edges were clear. The depth of the linear concave-convex pattern 2 was 160 μm, and although some thermal melting was observed, the pattern edges were good.
[0106] Example 2-2 (Print version) The surface protective film was peeled off from the "laminate having printing plate 1" prepared in the above [Example 1-1], and the printing plate 1 was subjected to laser engraving using the following ultrashort pulsed laser light to obtain a printing plate. Laser engraving was performed on the printing plate 1 of Example 1-1 above, but the laser engraving conditions of Example 1-2 above were changed to the following conditions: laser repetition frequency: 1 MHz, pulse width: 1 picosecond, average output: 20 W, overlap rate: 90%, and energy per pulse: 20 μJ. The resulting line-shaped concave-convex pattern 1 had a depth of 240 μm and had clear pattern edges. The line-shaped concave-convex pattern 2 had a depth of 80 μm and had clear pattern edges.
[0107] Example 3-2 (Print version) The surface protective film was peeled off from the "laminate having printing plate 1" prepared in the above [Example 1-1], and the printing plate 1 was subjected to laser engraving using the following ultrashort pulsed laser light to obtain a printing plate. Laser engraving was performed on the printing plate 1 under the same laser engraving conditions as in Example 1-2, except that the laser repetition frequency was 2.5 MHz, the pulse width was 1 picosecond, the average output was 4.8 W, the overlap rate was 98%, and the energy per pulse was 4.8 μJ. The resulting line-shaped uneven pattern 1 had a depth of 125 μm and had clear pattern edges. The line-shaped uneven pattern 2 had a depth of 42 μm and had clear pattern edges.
[0108] Example 4-2 (Print version) The surface protective film was peeled off from the "laminate having printing plate 1" prepared in the above [Example 1-1], and the printing plate 1 was subjected to laser engraving using the following ultrashort pulsed laser light to obtain a printing plate. For the printing plate 1, the laser engraving of the fine pattern was performed under the laser engraving conditions of Example 1-2 above, by converting the fundamental wave of 1064 nm of a YAG laser, an end-pumped semiconductor laser-pumped Q-switched solid-state laser, "IceFyre 1064-50" (Spectra-Physics, Inc., trademark), to a second harmonic wave of 515 nm using a harmonic generator / pulse selector "SHG" (Spectra-Physics, Inc., trademark), and concentrating the beam diameter to 8 μm using a lens. The conditions were changed to a laser repetition rate of 1 MHz, a pulse width of 1 picosecond, an average output of 5 W, an overlap rate of 96.9%, a lens NA of 0.070, a focus depth of 0.100 mm, and an energy per pulse of 5 μJ. The sample to be engraved (sheet-shaped printing plate) was fixed, and the laser beam was moved by a galvanometer mirror to form a checkerboard pattern consisting of multiple concave and convex patterns. The M2 value, which indicates the quality of the beam, was less than 1.8. A condenser lens with an f-number of 100 mm was used for the output light, and the position was controlled so that the laser focus was on the inside of the printing plate. The laser processed pattern had a depth of 115 μm for the concave-convex pattern 1 and clear pattern edges. The line-shaped concave-convex pattern 2 had a depth of 40 μm and some thermal melting was observed, but the pattern edges were good. The pattern edges were clear.
[0109] Example 5-1 (Laminate having a printing plate) First, a laminate provided with a printing original plate 2 was produced from the "laminate 2 before exposure" obtained in the above (Production Example 2). After exposure, the photosensitive resin composition layer 2 constituting the "laminate 2 before exposure" becomes the original printing plate 2 by peeling off the surface protective film. The exposure conditions used were the same as those in Example 1-1. In this example, the MFR of the photosensitive resin composition 2 having a support and a surface protection film on the top and bottom surfaces after exposure was 0.2 g / 10 min, which was less than half of the MFR before exposure, and it was confirmed that the composition had cured. The storage modulus (G') was 5.00 x 10 5 Pa, the laser light transmittance at the laser wavelength (1064 nm) was 92%, the light transmittance at the laser wavelength (515 nm) was 84%, and the light transmittance at the laser wavelength (343 nm) was 18%.
[0110] Example 5-2 (Print version) The surface protective film was removed from the "laminate having the printing original plate 2" prepared in the above-mentioned [Example 5-1], and the printing original plate 2 was subjected to laser engraving using the following ultrashort pulsed laser light to obtain a printing plate. Laser engraving was carried out on the printing plate 2 under the laser engraving conditions described in Example 1-2 above. The resulting line-shaped concave-convex pattern 1 had a depth of 320 μm and had clear pattern edges, while the line-shaped concave-convex pattern 2 had a depth of 110 μm and had good pattern edges although some thermal melting was observed.
[0111] Example 6-2 (Print version) The surface protective film was peeled off from the "laminate having the printing original plate 2" prepared in the above [Example 5-1], and the printing original plate 2 was subjected to laser engraving using the following ultrashort pulsed laser light to obtain a printing plate. Laser engraving was carried out on the printing plate 2 under the laser engraving conditions described in Example 4-2 above. The resulting line-shaped uneven pattern 1 had a depth of 70 μm and had clear pattern edges. The line-shaped uneven pattern 2 had a depth of 40 μm and had clear pattern edges.
[0112] Example 7-1 (Laminate having a printing plate) First, a laminate provided with a printing original plate 3 was produced from the "laminate 3 before exposure" obtained in the above (Production Example 3). After exposure, the photosensitive resin composition layer 3 constituting the "laminate 3 before exposure" becomes the printing blank 3 by peeling off the surface protective film. The exposure conditions used were the same as those in Example 1-1. In this example, the MFR of the photosensitive resin composition 3 having a support and a surface protection film on the top and bottom surfaces after exposure was 18.0 g / 10 min, which was less than half of the MFR before exposure, and therefore it was confirmed that the composition had cured. The storage modulus (G') was 4.3 x 10 4 Pa, the laser light transmittance at the laser wavelength (1064 nm) was 95%, the light transmittance at the laser wavelength (515 nm) was 73%, and the light transmittance at the laser wavelength (343 nm) was 55%.
[0113] Example 7-2 (Print version) Laser engraving was performed on the printing plate 3 of Example 7-1 above, but the laser engraving conditions were changed from those of Example 4-2 above to the following conditions: laser repetition frequency: 0.4 MHz, pulse width: 25 picoseconds, average output: 4 W, overlap rate: 50%, and energy per pulse: 400 μJ. The resulting line-shaped uneven pattern 1 had a depth of 56 μm and had clear pattern edges. The line-shaped uneven pattern 2 had a depth of 19 μm and had clear pattern edges.
[0114] Example 8-2 (Print version) The surface protective film was peeled off from the "laminate having printing plate 1" prepared in the above [Example 1-1], and the printing plate 1 was subjected to laser engraving using the following ultrashort pulsed laser light to obtain a printing plate. Among the laser engraving conditions of the above-mentioned [Example 1-2], the laser engraving of the fine pattern was performed on the printing plate 1 using a disk-type ultrashort pulse semiconductor laser "TruMicro5380" (trademark, manufactured by TRUMPF) by concentrating a triple wave 343 nm beam diameter to 8 μm with a lens. The conditions were changed to 1 MHz laser repetition frequency, 1 picosecond pulse width, 20 W average output, 90.0% overlap rate, 0.037 lens NA, 0.050 mm focus depth, and 20 μJ energy per pulse. The depth of the obtained line-shaped concave-convex pattern 1 was 53 μm, and the pattern edges were clear. The depth of the line-shaped concave-convex pattern 2 was 18 μm, and the pattern edges were clear.
[0115] Comparative Example 1-1 (Laminate having a printing plate) First, a laminate equipped with a printing original plate 5 was produced from the "laminate 5 before exposure" obtained in the above (Production Example 5). The photosensitive resin composition layer 5 constituting the "laminate 5 before exposure" becomes the printing original plate 5 after exposure. The exposure conditions used were the same as those in Example 1-1. In this example, the MFR of the photosensitive resin composition 5 having a support and a surface protection film on the top and bottom surfaces after exposure was 32.0 g / 10 min. Since the MFR did not change compared to before exposure, it was confirmed that the composition was not cured. The storage modulus (G') was 5.1 x 10 6Pa, the laser light transmittance at the laser wavelength (1064 nm) was 95%, the light transmittance at the laser wavelength (515 nm) was 84%, and the light transmittance at the laser wavelength (343 nm) was 3%.
[0116] Comparative Example 1-2 (Print version) The uncured "laminate 5 having printing original plate 5" in the above [Comparative Example 1-1] was subjected to laser engraving using the following ultrashort pulsed laser light with the surface protective film removed to obtain a printing plate. Laser engraving was carried out under the laser engraving conditions described in Example 1-2 above. The depth of the obtained line-shaped concave-convex pattern 1 was 28 μm, and the depth of the pattern 2 was 9 μm. The engraved depth was insufficient, and the obtained pattern was dissolved and unclear.
[0117] Comparative Example 2-1 (Laminate having a printing plate) First, a laminate provided with a printing original plate 6 was produced from the "laminate 6 before exposure" obtained in the above (Production Example 6). The photosensitive resin composition layer 6 constituting the "laminate 6 before exposure" becomes the printing blank 6 after exposure. The exposure conditions used were the same as those in Example 1-1. In this example, the MFR of the photosensitive resin composition 6 having a support and a surface protection film on the top and bottom surfaces after exposure was 25 g / 10 min. Since the MFR did not change compared to before exposure, it was confirmed that the composition had not hardened. The storage modulus (G') was 4.3 × 10 4 Pa, the laser light transmittance at the laser wavelength (1064 nm) was 95.0%, the light transmittance at the laser wavelength (515 nm) was 96.0%, and the light transmittance at the laser wavelength (343 nm) was 18.0%.
[0118] Comparative Example 2-2 (Print version) The uncured printing plate 6 of the "laminate having the printing plate 6" prepared in the above [Comparative Example 2-1] was laser engraved using the following ultrashort pulsed laser light to obtain a printing plate. Laser engraving was carried out under the laser engraving conditions described in Example 1-2 above. The resulting line-shaped concave-convex pattern 1 had a depth of 32 μm, while the depth of pattern 2 was 11 μm, meaning that the engraved depth was insufficient and a satisfactory pattern was not obtained.
[0119] Comparative Example 3-1 (Laminate having a printing plate) First, a laminate provided with a printing original plate 7 was produced from the "laminate 7 before exposure" obtained in the above (Production Example 7). The photosensitive resin composition layer 7 constituting the "laminate 7 before exposure" becomes the printing blank 7 after exposure. The exposure conditions used were the same as those in Example 1-1. In this example, the MFR of the photosensitive resin composition 7 having a support and a surface protection film on the upper and lower surfaces after exposure was 42 g / 10 min. Since the MFR did not change compared to before exposure, it was confirmed that the composition had not hardened. The storage modulus (G') was 3.0×10 4 Pa, the laser light transmittance at the laser wavelength (1064 nm) was 45.0%, the light transmittance at the laser wavelength (515 nm) was 4.0%, and the light transmittance at the laser wavelength (343 nm) was 4.0%.
[0120] Comparative Example 3-2 (Print version) The uncured printing plate 7 of the "laminate having printing plate 7" was laser engraved using the ultrashort pulsed laser beam described below to obtain a printing plate. Laser engraving was carried out under the laser engraving conditions described in Example 1-2 above. The resulting line-shaped concave-convex pattern 1 had a depth of 25 μm, while the depth of pattern 2 was 8 μm, so the engraved depth was insufficient and a good pattern was not obtained.
[0121] [Table 1]
[0122] [Table 2]
[0123] This application is based on a Japanese patent application (Patent Application No. 2020-042098) filed with the Japan Patent Office on March 11, 2020, the contents of which are incorporated herein by reference. [Industrial Applicability]
[0124] The laminate and printing plate manufacturing method of the present invention have wide industrial applicability in the general commercial printing field.
Claims
1. A support, a printing original plate, and a protective film are included. the printing original plate includes a resin cured product obtained by exposing the entire surface of the photosensitive resin on the side facing the protective film to light and curing the resin, and has a storage modulus G' at 140°C of 5.00 x 104 Pa or more and 1.00 x 106 Pa or less; On the surface of the printing plate of the laminate, A laser engraving process is included in which a concave-convex pattern is formed using ultrashort pulsed laser light. The overlap rate of successive pulses of the ultrashort pulsed laser light is 50% or more and 99% or less. A method for manufacturing a printing plate.
2. A printing plate having a support, a printing original plate, and a protective film, the printing original plate includes a resin cured product obtained by exposing the entire surface of the photosensitive resin on the side facing the protective film to light and curing the resin, and has a storage modulus G' at 140°C of 5.00 x 104 Pa or more and 1.00 x 106 Pa or less; On the surface of the printing plate of the laminate, A laser engraving process is included in which a concave-convex pattern is formed using ultrashort pulsed laser light. In the step of forming a concave-convex pattern on the surface of the printing original plate by the ultrashort pulsed laser light, a lens having a numerical aperture (NA) of 0.010 or more and 0.100 or less is used. A method for manufacturing a printing plate.
3. A printing plate having a support, a printing original plate, and a protective film, the printing original plate includes a resin cured product obtained by exposing the entire surface of the photosensitive resin on the side facing the protective film to light and curing the resin, and has a storage modulus G' at 140°C of 5.00 x 104 Pa or more and 1.00 x 106 Pa or less; On the surface of the printing plate of the laminate, A laser engraving process is included in which a concave-convex pattern is formed using ultrashort pulsed laser light. the focus depth of the ultrashort pulsed laser light is 25 μm or more and 700 μm or less from the surface of the printing plate; A method for manufacturing a printing plate.
4. The printing plate precursor is The wavelength of the ultrashort pulsed laser light used in the laser engraving process is: The light transmittance is 10% or more and 99.9% or less. The method for producing a printing plate according to any one of claims 1 to 3.
5. The printing plate precursor is The wavelength of the ultrashort pulsed laser light used in the laser engraving process is: The light transmittance is more than 75% and is not more than 99.9%. The method for producing a printing plate according to any one of claims 1 to 4.
6. The average output of the light source of the ultrashort pulse oscillation laser light used in the laser engraving step is 0.01 W or more and less than 1000 W. The method for producing a printing plate according to any one of claims 1 to 5.
7. The pulse width of the ultrashort pulse oscillation laser light used in the laser engraving process is 1 femtosecond or more and 200 nanoseconds or less. The method for producing a printing plate according to any one of claims 1 to 6.
8. The oscillation wavelength of the ultrashort pulse oscillation laser light used in the laser engraving step is 300 nm or more and 1.5 μm or less. A method for producing a printing plate according to any one of claims 1 to 7.
9. The oscillation wavelength of the ultrashort pulsed laser light used in the laser engraving step is 300 nm or more and less than 700 nm. A method for producing a printing plate according to any one of claims 1 to 8.
10. The energy per pulse of the ultrashort pulse oscillation laser light used in the laser engraving step is 1 μJ or more and 100 kJ or less. A method for producing a printing plate according to any one of claims 1 to 9.
11. The method for producing a printing plate according to claim 1 , wherein the ultrashort pulsed laser light used in the laser engraving step has a repetition frequency of 20 kHz or more and 500 MHz or less.
Citation Information
Patent Citations
Processless computer to plate precursor, and ultra-short pulse laser plate making method
CN106543860A
Method and device for generating a printed image on a printing block blank
DE102015009950A1
Multicolor imaging using multiphoton photochemical processes
JP2004503826A
Platemaking apparatus for printing plate
JP2006227261A
Direct engraving of flexographic printing plates
JP2009541091A